Using fracture scarp intersection lineations as kinematic indicators on active normal fault scarps - Billy J. Andrews; Zoë K. Mildon; Manuel L. Diercks; Sam Mitchell; Gerald P. Roberts; Constanza Rodriguez Piceda; Jenni Robertson (Journal of Structural Geology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Grazing by wild and domestic ungulates reduces floral resources and native bee abundance in a multi-use landscape - Will Glenny; Sandra J. DeBano; Mary M. Rowland; Scott R. Mitchell; Skyler Burrows; Michael J. Wisdom; Joshua P. Averett; Bridgett Naylor (Biological Conservation, 2026)

Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Mechanical jamming in pseudotachylyte-hosted breccias - David P. Dobson; Charlotte L. Bays; Thomas M. Mitchell (Tectonophysics, 2026)

Constructed value of information with iterative scoring and parametric uncertainty to identify management‐relevant research priorities for a declining raptor species - Kristin P. Davis; Mitchell J. Eaton; Emily R. Bjerre; Hillary M. White; Clint W. Boal; Jennifer H. Herner‐Thogmartin; Orin J. Robinson; Abigail J. Lawson (Conservation Biology, 2026)
Constructed value of information (CVoI) is an expert elicitation decision‐analytic tool used to prioritize sources of uncertainty based on their potential to improve decision outcomes if resolved. Despite increased application of CVoI, the robustness of CVoI prioritization of sources of uncertainty relative to differences in expert elicitation and scoring methods has not been evaluated. We engaged a group of species experts in a decision‐analytic process to elicit uncertainties, framed as alternative hypotheses, about current population declines of the American kestrel ( Falco sparverius ) in the United States. Participants scored 13 hypotheses across 3 CVoI criteria, which are defined as constructed scales. Rather than experts selecting a single score per criterion, we used a likelihood point method to incorporate parametric uncertainty in the scoring process, in which experts were given 100 points to distribute across possible score categories within the criterion‐specific constructed scale. Experts provided scores over 2 scoring rounds, with an opportunity to review and discuss initial scores between rounds. We used a Shannon entropy calculation to quantify how evenly participants allotted their points. We used simulation to evaluate the robustness of our prioritization results relative to a scoring method in which participants selected a single score category for each criterion. Participants often spread their points across 2 adjacent scores, reflecting parametric uncertainty. For one third of the hypothesis‐scoring round combinations, the prioritization results differed in approximately 50% of simulations. The highest scoring hypotheses related to how the use of artificial versus natural nest cavities affects fecundity or survival, whether winter roosting sites are a limiting factor for population growth, and whether gamebird habitat management may benefit kestrel populations. Our CVoI prioritization framework can be used to develop collaborative research that is directly relevant to a management decision and is an advance in eliciting more representative expert beliefs.

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part Two: non-parasitic conditions - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

The clinical and laboratory features of Capnocytophaga infection - P. Davies; E. Mitchell; A. Deshpande (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Drivers of fine-scale space use and grazing patterns of juvenile parrotfish on western Atlantic reefs - David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Manuel González-Rivero; Alastair R. Harborne (Coral Reefs, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crop mixtures: yield responses to climate and management and impacts on seed and soil chemical composition in a Scottish-based study - R. Brooker; R. J. Pakeman; R. L. Hewison; C. Mitchell; A. C. Newton; R. Neilson; S. Raubach; P. D. Shaw; S. Verrall; A. J. Karley (Plant and Soil, 2026)
Introduction Crop mixtures can be an important part of the toolkit for maintaining crop production while addressing the climate and nature crises. However, uncertainties around some issues may prevent their uptake. Research question This study addressed several uncertainties, specifically the response of mixture yields to climate and management, and the impacts of mixed cropping on seed chemical composition, soil carbon and nutrients. Materials and methods We undertook 32 intercropping trials between 2020 and 2022 on both commercial and research farms. These varied in design, management and crop combinations, with mixture choice often determined by farmers. We assessed multiple responses including yield, weed cover, and seed and soil chemical composition. Results and conclusions When compared to monocultures, yield gains from growing a crop mixture were roughly 20% based on Crop Performance Ratio (CPR). We found limited impacts of mixture diversity and composition on seed chemical composition, influences of management on weed control, and enhanced crop mixture performance under cooler conditions with lower rainfall. We also found varying mixture performance depending on mixture composition. Importantly, irrespective of management, climate, and composition effects, crop mixtures always performed at least as well as expectations based on monocultures. Even without further refinement from, for example, targeted breeding, crop mixtures provide reliable crops without yield losses or (for parameters tested) substantial changes in seed chemistry. However, detected reductions in organic matter in upper soil layers indicate a priority for future research is understanding crop mixture impacts on soil carbon dynamics in both shallow and deep soils.

Is circularity going to shrink the global economy? Theoretically, yes - Julian Kirchherr; Mitchell P. Jones (Journal of Industrial Ecology, 2026)
The circular economy (CE) was originally promoted as a framework capable of reconciling economic growth with environmental protection, but scholarship is now divided between techno-optimist perspectives that interpret CE as a pathway to green growth and degrowth approaches that regard it as inherently post-growth. This paper employs a first-principles conceptual approach to examine the macroeconomic mechanisms linking circularity and growth. By grounding the discussion in basic economic identities and material flow logic, it clarifies how reductions in throughput affect economic output and material stock across scales. The argument demonstrates that CE is contractionary in principle but stabilizing in practice: when implemented fully and globally, it constrains GDP through declining material flows, while partial and incremental adoption within existing institutions enhances efficiency, resilience, and welfare without systemic disruption. The divergence between techno-optimist and degrowth positions thus reflects differences in temporal and analytical framing rather than opposing evidence. Both positions also recognize that the current economic system is environmentally unsustainable. The limitations of the CE discussed in this paper suggest that it should be understood as a bridge paradigm that maintains short-term stability and highlights the need for continued research into economic models that extend beyond CE and its growth-based foundations.

The past is prologue: contemporary and historical genetic variation in a bighorn sheep metapopulation - E. Frances Cassirer; Soraia Barbosa; Kimberly R. Andrews; Nathan Borg; Jennifer R. Adams; Hollie Miyasaki; Michael S. Mitchell; Lisette P. Waits (Conservation Genetics, 2026)

Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.

Managing Radiation Therapy Treatment Delivery Challenges: Impact of an Interprofessional Educational Series for Radiation Therapists and Radiation Oncology Residents - Jordan McDonald; Denise De La Cruz; Chelsea C. Pinnix; Julianna K. Bronk; Comron Hassanzadeh; Emma B. Holliday; Anna Lee; Melissa P. Mitchell; Devarati Mitra; Subha Perni; Nicolette Taku; Jillian R. Gunther (Journal of Cancer Education, 2026)

Distributional patterns and habitat associations of sturgeon chub in western Missouri River tributaries of South Dakota - Mitchell R. Magruder; Jenna P. Ruoss; Mark A. Pegg (Journal of Fish Biology, 2026)
There is a growing body of literature that suggests riverine fish are some of the most threatened taxa on a global scale. Similarly, the literature suggests less‐altered tributaries may offer refugia for large‐river specialists. The greater Mississippi River basin, including the Missouri River system, has been subjected to anthropogenic changes in flow, habitat fragmentation and turbidity, leading to declines in multiple native fish species. Small‐bodied fish species are exceptionally susceptible to changes in habitat, resulting in a heightened risk of extinction. The sturgeon chub Macrhybopsis gelida belongs to the family Leucisidae and is a benthic, small‐bodied minnow native to the greater Mississippi River basin and is highly adapted for life in large, turbid and free‐flowing rivers. Sturgeon chub distribution, habitat use and associations with other species are well studied in large mainstem rivers, but remain poorly understood in tributaries, which may serve as refugia as mainstem populations decline. Evidence of recent declines in the upper Missouri River highlights the need to better understand the role of these tributary systems. We therefore assessed the distribution and abundance of sturgeon chub populations in western Missouri River tributaries of South Dakota, evaluated broad‐scale abiotic and biotic influences on their distributional patterns and characterized their habitat associations. Sturgeon chub were captured in the Cheyenne ( n = 81), White ( n = 331) and Little White ( n = 71) rivers but were absent from the Little Missouri and Grand rivers. Sturgeon chub distributions were limited to lower areas of all rivers (i.e. closer proximity to mouths) where stream width, turbidity, discharge and observed habitat complexity (i.e. greater diversity of mesohabitats present) were highest. Furthermore, sturgeon chub were often found in association with high abundances (≥10% of catch) of flathead chub Platygobio gracilis and Hybognathus spp. (plains minnow Hybognathus placitus and western silvery minnow Hybognathus argyritis ). Sturgeon chub generally used main‐ or secondary‐flowing macrohabitats and were predominantly found in channel border or thalweg mesohabitats in most sampled reaches. Mesohabitats with greater bottom velocities [mean = 0.34 m/s, standard deviation (SD) = 0.11] and higher percentages of gravel (mean = 44, SD = 24) in the substrate were more likely to contain sturgeon chub in the White and Little White rivers, whereas greater depths (mean = 0.49 m, SD = 0.19) were associated with their presence in the Cheyenne River. Our study highlights the importance of tributaries as a surrogate to the mainstem Missouri River regarding sturgeon chub persistence that may be applicable to other imperilled fish species.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part One: parasites - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Associations between cognitive frailty and circulating cardiovascular biomarkers in a memory clinic cohort - Xin Tong Tan; Joyce R. Chong; Eddie J. Y. Chong; Ming Ann Sim; Jiangbo Cui; Siew Pang Chan; Oi Wah Liew; Boon Yeow Tan; Narayanaswamy Venketasubramanian; Arthur Mark Richards; Mitchell K. P. Lai; Christopher Li-Hsian Chen (GeroScience, 2026)

Transforming textile waste into materials using fungi - Maidu Silm; Qixiang Jiang; Anu Kisand; Alexander Bismarck; Mitchell P. Jones (Resources, Conservation and Recycling, 2026)

Reframing law and behavior for circular economies - Alessandro Creazza; Roland Geyer; Mitchell P. Jones; Tamar Makov; Nicola Saccani; Gerald Shurson; Katrien Steenmans; Andrea Urbinati (Resources, Conservation and Recycling, 2026)

Circular metrics as instruments for quantifying sustainability - John D. Atkinson; Thomas Elliot; Mitchell P. Jones; Julian Kirchherr; Ana T. Lima; Mugur Schuppler; Dominik Wiedenhofer (Resources, Conservation and Recycling, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Artificial intelligence as an agent of circular transition - Kirolos Abdou; Yi Bao; Mitchell P. Jones; Nils Kroell; Tom O. McDonald (Resources, Conservation and Recycling, 2026)

Legacy effects of cover crops on weed biomass and yield of the subsequent corn crop - Barbara Baraibar; Brosi A. Bradley; Mitchell C. Hunter; Charles M. White; Denise M. Finney; Jason P. Kaye; Megan E. Schipanski; David A. Mortensen (European Journal of Agronomy, 2026)

Depth affects the population dynamics on a soft coral-dominated reef on the Great White Wall, Fiji - Nile P. Stephenson; Katie M. Delahooke; Charlotte G. Kenchington; Jone Waitaiti; Alice A. Ball; Victor E. Bonito; Andrea Manica; Emily G. Mitchell (Coral Reefs, 2026)
Soft corals (order Alcyonacea) are an important component of tropical coral reefs, and often form locally abundance dense carpets. Some soft coral species are prone to bleaching and heat stress like scleractinian, reef-forming corals, but others appear resistant to bleaching stressors. Despite the importance of soft corals in tropical reefs, there is limited knowledge regarding their demographic ecology. Spatial point process analysis (SPPA) enables inference of ecological processes underlying spatial distributions of individuals in a community by investigating the fit of models of known processes to observed spatial patterns. SPPA can also quantify how these underlying ecological processes change with environmental gradients (such as depth). We used SPPA to investigate the population ecology on the Great White Wall (GWW), Fiji—a vertical reef dominated by Nephtheidae soft corals alongside other filter feeders and algae. We found that a combination of reproductive and habitat association processes best explained the spatial patterns on the GWW. We found that the best-fit underlying ecological processes changed with depth, and that Nephtheidae soft corals became more dominant on deeper parts of the wall, likely due to a combination of reproductive lability, fast growth rates, and increasing suitable habitat associated with filter-feeding. Even where the Nephtheidae were most dominant, other filter feeders were able to persist. This mixed community composition could be because the Nephtheidae feed in periods of high current, and temporal niche partitioning in feeding could be permitting biodiversity on the GWW, allowing for hydroids and sponges to coexist with the Nephtheidae.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Curated dialogue: a new article format from the RCR webinar program - Mitchell P. Jones; Ming Xu (Resources, Conservation and Recycling, 2026)

Hybrid modeling for daily streamflow forecasting: A study over the contiguous United States - Fanzhang Zeng; Zhao Zhao; Natalie P. Memarsadeghi; Charles J. McKnight; Xudong Wang; Sarah Miele; Mayank Chadha; Dania Ammar; Yichao Zeng; Magdalena Asborno; Kenneth Mitchell; Guga Gugaratshan; et al. (Journal of Hydrology, 2026)

Deep learning model for fast, science-based forecasting of fluid migration along faults in geologic carbon storage scenarios - Hyeonseok Lee; Paul E. Kim; Shaowen Mao; Shuojia Fu; Axel P. Indro; Seunghwan Baek; Nate Mitchell; Mohamed Mehana (International Journal of Greenhouse Gas Control, 2025)

A defense of the circular economy - Julian Kirchherr; Mitchell P. Jones; Martin Geissdoerfer; Matthew Coffay (Journal of Industrial Ecology, 2025)
The notion of circular economy (CE) has been trending among policymakers, businesses, and academia for over a decade. Sometimes poorly understood and often misrepresented as a one‐size‐fits‐all solution to environmental problems without economic trade‐offs, the concept has recently drawn considerable criticism. According to its critics, the CE (1) rebrands existing concepts without clarity, (2) makes unrealistic environmental promises, (3) oversimplifies and overlooks critical factors, (4) clashes with societal values and norms, (5) fails in practical business applications, and (6) serves as a capitalist tool for Western interests. In this paper, we critically review these criticisms of the CE, many of which are not based on empirical realities, are obsolete, or originate in oversimplified interpretations of the circle metaphor. We argue that CE is an “umbrella” framing for existing concepts with a relatively concrete definition. Formerly corporate led, CE has matured into an academically dominated field, backed by substantial technical literature, new sub‐fields led by social scientists, and an increasingly advanced and detailed understanding of previous simplifications. Empirical evidence is emerging that CE can be operationalized and scaled, provide considerable environmental benefits, and can align with societal values and priorities. While easy to criticize, the hope and momentum that the CE has sparked is creating tangible benefits over other sustainability‐oriented concepts. Further research is required to establish its long‐term advantages, drawbacks, and complementarities with alternative approaches.

Evolving physical and mechanical rock properties during exposure at Earth's surface - Monica Rasmussen; Martha Cary Eppes; Yang Yuan; Philip G. Meredith; Karin Hofer Apostolidis; Thomas Mitchell; Alex J. Rinehart; Amit Mushkin; Patrick Webb; Valerie Reynolds; Alan J. Hidy; Samantha Berberich; et al. (Geomorphology, 2025)

A modified-live Mannheimia haemolytica expressing Mycoplasma bovis EFTu and Hsp70 induced systemic and mucosal antibody responses in American bison but failed to fully protect against Mycoplasma bovis challenge. - Bryan S. Kaplan; Rohana P. Dassanayake; Bradley O. Chriswell; William D. Boatwright; Steven C. Olsen; Mitchell V. Palmer; Paola M. Boggiatto; Carly R. Kanipe; Eduardo Casas; Robert E. Briggs; Fred M. Tatum (Veterinary Microbiology, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Why is Biomarker Assay Validation Different from that of Pharmacokinetic Assays? - Yan G. Ni; Lauren F. Stevenson; Lakshmi Amaravadi; Carmen Fernández-Metzler; Lindsay King; Steven P. Piccoli; Amanda Hays; Dhiman Ghosh; Sarah Mitchell Bean; Stephanie Cape; Enrique A. Dalmasso; Shashank Gorityala; et al. (The AAPS Journal, 2025)

The Fundamentals of the Analysis of Cascade Impactor Data for the Characterization of Aerodynamic Particle Size Distributions (APSDs) in the Testing of Orally Inhaled Drug Products (OIPs) - Daryl L. Roberts; Jolyon P. Mitchell (AAPS PharmSciTech, 2025)

P12-35 From neat compounds to complex mixtures: Microphysiological systems for cardiotoxicity safety testing of botanical extracts - M. Gossmann; A. Monteiro da Rocha; S. Zhao; J. Krzykwa; C. Mitchell; J. Wu; P. Linder (Toxicology Letters, 2025)

Multi-millennia slip rate relationships between closely spaced across-strike faults: Temporal earthquake clustering of the Skinos and Pisia Faults, Greece, from in situ 36Cl cosmogenic exposure dating - Sam Mitchell; Claudia Sgambato; Jenni Robertson; Gerald P. Roberts; Joanna P. Faure Walker; Zoë Mildon; Athanassios Ganas; Ioannis Papanikolaou; Francesco Iezzi; Joakim Beck; Steven A. Binnie; Tibor Dunai; et al. (Journal of Structural Geology, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Ultrasensitive Staphylococcal Enterotoxin B Quantum Dot-Based Lateral Flow Immunoassays for Rapid Testing of Poultry Rinsates and Milk - Lance P. Ford; Skyler B. Sutton; Daniel R. Mitchell; John G. Bruno (Journal of Fluorescence, 2025)

Variation of population and community ecology over large spatial scales in Ediacaran early animal communities - Emily G. Mitchell; Nile P. Stephenson; Princess A. Buma-at; Lucy Roberts; Sasha Dennis; Charlotte G. Kenchington (Global and Planetary Change, 2025)

Heat-set gelation of milk- and fermentation-derived β-lactoglobulin variants - Zheng Pan; Remco Kornet; Sheelagh Hewitt; Alan Welman; Jeremy P. Hill; Marcel Wubbolts; Stephen Mitchell; Warren C. McNabb; Aiqian Ye; Alejandra Acevedo-Fani; Skelte G. Anema (Food Hydrocolloids, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Priming the decomposition of cover crop residues in no-till organic cropping systems - Delaney A. Sondag; Amélie C.M. Gaudin; Jeffery P. Mitchell; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2025)

Early Childhood Nutrition-Related Policy, System, and Environmental-Focused Evaluation: A Qualitative Study Exploring Knowledge, Barriers, and Opportunities - Elder Garcia Varela; Alaina M. Mitchell; Isabella Bolivar; Megan A. McVay; Karla P. Shelnutt; David Miller; Amy R. Mobley (Journal of Nutrition Education and Behavior, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Fluid pressure fluctuations and the seismic signature of a fault-controlled fluid migration pulse - Ashley Stanton-Yonge; Almudena Sánchez De La Muela; Rebecca K. Pearce; James O.S. Hammond; Thomas M. Mitchell; Stephen P. Hicks; W. Ashley Griffith; Max Moorkamp; Philip G. Meredith; José Cembrano (Earth and Planetary Science Letters, 2025)

Ecological resources of a heavily modified and utilised temperate coastal embayment: Cockburn Sound - Peter J. Mitchell; Daniel E. Yeoh; Kurt N. Krispyn; Claire N. Greenwell; Sorcha Cronin-O’Reilly; Delphine B.H. Chabanne; Glenn A. Hyndes; Danielle Johnston; David V. Fairclough; Claire Wellington; Alan Cottingham; Gary Jackson; et al. (Frontiers in Marine Science, 2025)
Coastal environments and their associated biota provide numerous environmental, economic and societal services. Cockburn Sound, a temperate embayment on the lower west coast of Western Australia, is immensely important for the State and adjacent capital city of Perth. However, urbanisation and associated terrestrial and marine development has the potential to threaten this important ecosystem. This study collated published and unpublished data to review the current state of the ecological resources of Cockburn Sound and describe how they have changed over the past century. Post-WWII, the embayment began undergoing pronounced anthropogenic changes that limited oceanic water exchange, increased nutrient load, modified benthic habitats and increased fishing pressure. The most visual outcome of these changes was substantial eutrophication and the loss of 77% of seagrass habitats. However, the increased primary productivity from elevated nutrient inputs produced high commercial fishery yields of up to ~1,700 t in the early 1990s before improved wastewater regulation and restricted fishing access steadily reduced commercial catches to ~300 t in recent years. Despite substantial anthropogenic-induced changes, Cockburn Sound has remained a diverse and ecologically important area. For example, the embayment is a key spawning area for large aggregations of Snapper, is a breeding and feeding site for seventeen marine bird species (including Little Penguins) and, is frequented by numerous protected species such as pinnipeds, dolphins, and White and Grey Nurse sharks. In recent decades, numerous projects have been initiated to restore parts of Cockburn Sound with mixed success, including seagrass transplantation, deployment of artificial reefs and stocking of key fish species, mainly Snapper. Nevertheless, while still biodiverse, there are signs of considerable ecological stress from escalating anthropogenic pressures and the cumulative impacts of ongoing and future developments, including climate change, which may severely impact the functioning of this important ecosystem.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Proposals for Global Harmonization of Regulations for Testing of Spacers and Valved Holding Chambers for Pressurized Metered Dose Inhalers - Jolyon P. Mitchell (AAPS PharmSciTech, 2025)

Temperament and state-dependent behaviours in large herbivores - Heather N. Abernathy; Rebecca L. Levine; Yasaman N. Shakeri; Jaron T. Kolek; Brittany L. Wagler; Rachel A. Smiley; Rhiannon P. Jakopak; Mitchell J. Brunet; Rebekah T. Rafferty; Seth T. Rankins; Katey S. Huggler; Brandon Scurlock; et al. (Animal Behaviour, 2025)

Amadeus: Accessing and analyzing large scale environmental data in R - Mitchell Manware; Insang Song; Eva S. Marques; Mariana Alifa Kassien; Lara P. Clark; Kyle P. Messier (Environmental Modelling & Software, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Contrasting population declines and drivers of ecological refuge for two range-restricted amphibians - Emily P. Hoffmann; Kim Williams; Christine Taylor; Grzegorz Skrzypek; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Characterization and screening of new Metarhizium isolates to control the coconut rhinoceros beetle in the Pacific islands - Laura F. Villamizar; Gloria P. Barrera; Alphonse Luange; Katayo Sagata; Paul Gende; Simon Chris; Helen Tsatsia; Freda Mudu; Mitchell Weston; Chikako van Koten; Sarah Mansfield; Trevor A. Jackson; et al. (Fungal Biology, 2024)

The Calorimetric Electron Telescope (CALET) on the International Space Station: Results from the first eight years on orbit - Y. Akaike; O. Adriani; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Direct measurements of cosmic – Ray iron and nickel with CALET on the International Space Station - O. Adriani; Y. Akaike; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Large structural estuaries: Their global distribution and morphology - Mitchell P. Baum; David M. Kennedy; Sarah L. McSweeney (Geomorphology, 2024)

Development and characterisation of a novel complex triple cell culture model of the human alveolar epithelial barrier - Sarah M. Mitchell; Kirsty Meldrum; Joshua W. P. Bateman; Teresa D. Tetley; Shareen H. Doak; Martin J. D. Clift (In vitro models, 2024)
Owing to increased pressure from ethical groups and the public to avoid unnecessary animal testing, the need for new, responsive and biologically relevant in vitro models has surged. Models of the human alveolar epithelium are of particular interest since thorough investigations into air pollution and the effects of inhaled nanoparticles and e-cigarettes are needed. The lung is a crucial organ of interest due to potential exposures to endogenous material during occupational and ambient settings. Here, an in vitro model of the alveolar barrier has been created in preparation for use in the quasi-air liquid interface (qALI) and (aerosol) air–liquid interface (ALI) exposures. The model consists of an alveolar type 1-like cell line (TT1), an alveolar type 2-like cell line (NCI-H441) and a model of (alveolar) macrophages (dTHP-1). The model formulates a complex, multi-cellular system, cultured at the air–liquid interface, that mimics the apical layer of the alveolar epithelial region in the human lung. Characterisation data has shown that both TT1 and NCI-H441 epithelial cells are able to be cultured together in addition to dTHP-1 cells through imaging (morphology), pro-inflammatory response and viability measurements. This dataset also demonstrates evidence of a reasonable barrier created by the cell culture in comparison to negative controls. Furthermore, it shows that while maintaining a low baseline of (pro)-inflammatory mediator expression during normal conditions, the model is highly responsive to inflammatory stimuli. This model is proposed to be suitable for use in toxicology testing of inhaled exogenous agents.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Review: Artisanal Gold Mining in Africa—Environmental Pollution and Human Health Implications - Maureene Auma Ondayo; Michael J. Watts; Clive J. Mitchell; David C. P. King; Odipo Osano (Exposure and Health, 2024)
About nine million Artisanal and Small-scale Gold Mining (ASGM) workers in Africa and people living near ASGM activities are highly exposed to geogenic and anthropogenic potentially toxic elements (PTEs). Despite the hazards and risks posed by ASGM being well characterized, coordinated multidisciplinary environmental characterization with combined public health studies are limited, with often piecemeal and snapshot studies reported, as highlighted by this review. Furthermore, studies are often not connected with efforts to minimize hazards holistically. Given this, we systematically reviewed the scientific literature on human health hazards associated with ASGM in Africa through Google Scholar, Science Direct, and Pubmed databases. One hundred and seventy-three peer-reviewed papers published between 1996 and June 2023 from 30 African countries were identified. Toxicological environmental hazards were reported in 102 peer-reviewed papers, notably As, Cd, CN, Cr, Hg, Pb, respirable SiO 2 -laden dust, and radionuclides. Exposure to PTEs in human biomonitoring matrices and associated health impacts were documented in 71 papers. Hg was the most reported hazard. Gaps in research robustness, regulation and policy framework, technology, risk detection, surveillance, and management were found. Despite international and in-country mitigation efforts, ASGM-related hazards in Africa are worsening. This review paper highlights the need for coordinated action and multidisciplinary collaborative research to connect dispersed isolated studies to better characterize the associated disease burden associated with ASGM in Africa and sustainably maximize the wider benefits of ASGM whilst protecting public health and the environment.

Changes in soil N2O emissions and nitrogen use efficiency following long-term soil carbon storage: Evidence from a mesocosm experiment - Lindsey A. Kelley; Zhenglin Zhang; Santiago Tamagno; Mark E. Lundy; Jeffrey P. Mitchell; Amélie C.M. Gaudin; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Network analyses on photographic surveys reveal that invertebrate predators do not structure epibenthos in the deep (~2000m) rocky Powell Basin, Weddell Sea, Antarctica - Tasnuva Ming Khan; Huw J. Griffiths; Rowan J. Whittle; Nile P. Stephenson; Katie M. Delahooke; Autun Purser; Andrea Manica; Emily G. Mitchell (Frontiers in Marine Science, 2024)
Predator-prey interactions in marine ecosystems control population sizes, maintain species richness, and provide intermediate disturbance. Such ecosystem structuring interactions may be rare in Antarctic epibenthic communities, which are unique among marine ecosystems worldwide for their dominance of soft bodied fauna (sponges, soft and hard corals, and echinoderms) and a simultaneous paucity of shell crushing predators (sharks, rays and durophagous decapods). In the shallow benthos, instead of durophagy, important Antarctic predators such as starfish, pycnogonids (sea spiders), nemertean worms, and nudibranchs employ grazing, scavenging, or sucking strategies. Far less is known about deep sea (>1000 m) Antarctic benthic communities due to the challenging nature of polar data collection, so that photographic surveys provide one of the only means of making in situ observations of these deep sea communities. We used seabed photographs of the deep (~2000m) slope of the Powell Basin, northwest Weddell Sea, taken by the Ocean Floor Observation and Bathymetry System on board the RV Polarstern (PS118, April 2019) to investigate the epibenthic community composition, and Bayesian Network Inference (BNI) to determine the ecological network, namely the ecological associations, including potential invertebrate predator-prey relationships between taxa. Photographs show that the rocky substrates of the basin slope support between 10-22 morphotaxa per photo, and highly abundant communities (density between 106 to 553 individuals/m 2 ). BNI results reveal a network of associations between the sessile and mobile suspension and filter feeding organisms and their physical environment. However, associations between invertebrate predators like starfish, and other organisms, were not detected in the network. This lack of inclusion within the network suggests that, despite the presence of these normally important mobile predators, invertebrate predator-prey interactions on the rocky Powell Basin slope do not have the same ecosystem-regulating impact that they do on shallow Antarctic epibenthic communities.

Multistate outbreak of Salmonella Oranienburg infections linked to bulb onions imported from Mexico – United States, 2021 - Marvin R. Mitchell; Margaret Kirchner; Ben Schneider; Monica McClure; Karen P. Neil; Asma Madad; Temesgen Jemaneh; Mary Tijerina; Kurt Nolte; Allison Wellman; Daniel Neises; Arthur Pightling; et al. (Food Control, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

The relationship between kinematics and fault geometry for surface coseismic ruptures on across-strike faults: New observations of slip vectors and displacements along the Pisia and Skinos faults from the 1981 Eastern Gulf of Corinth, Greece earthquakes - Sam Mitchell; Gerald P. Roberts; Joanna P. Faure Walker; Francesco Iezzi; Claudia Sgambato; Jennifer Robertson; Zoë K. Mildon; Athanassios Ganas; Ioannis D. Papanikolaou; Elias J. Rugen (Journal of Structural Geology, 2024)

Implications and impacts of aligning regional agriculture with a healthy diet - Ryan T. Sharp; Angelina Sanderson Bellamy; Adrian Clear; Samantha Mitchell Finnigan; Ella Furness; Elliot Meador; Helen Metcalfe; Susanna Mills; Kevin Coleman; Andrew P. Whitmore; Alice E. Milne (Journal of Cleaner Production, 2024)

Unexpected obstacles in mechanical recycling of polypropylene labels: Are ambitious recycling targets achievable? - Jessica Schlossnikl; Elisabeth Pinter; Mitchell P. Jones; Thomas Koch; Vasiliki-Maria Archodoulaki (Resources, Conservation and Recycling, 2024)

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Biodegradable and conventional plastic packaging: Comparison of life cycle environmental impacts of poly(mandelic acid) and polystyrene - Harish K. Jeswani; Mitchell R. Perry; Michael P. Shaver; Adisa Azapagic (Science of The Total Environment, 2023)

Metabolomes of bumble bees reared in common garden conditions suggest constitutive differences in energy and toxin metabolism across populations - Ellen C. Keaveny; Mitchell R. Helling; Franco Basile; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Insect Physiology, 2023)

Comparative growth performance of backgrounded beef heifers treated with an injectable fixed-dose combination (0.2 mg/kg doramectin + 6.0 mg/kg levamisole hydrochloride) or single-active (0.2 mg/kg ivermectin) endectocide - Andrew A. DeRosa; Susan Holzmer; Jase J. Ball; Landon P. Watkins; Mitchell Blanding; Mark Alley; Thomas H. Short; David T. Bechtol; Audie R. Waite; Elizabeth J. Rigoni; Jezaniah K. Tena (Veterinary Parasitology, 2023)

Cutaneous apocrine gland neoplasia in 16 captive African wild dogs (Lycaon pictus) - Emily P. Mitchell; Melanie S. Henker; Karin Lemberger; Christine Gohl; Monir Majzoub-Altweck; Almuth Falkenau; Peter Caldwell; Baptiste Chenet; Marion Mosca; Didier Pin; Daniela Denk (Journal of Comparative Pathology, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Laboratory Performance Testing of Aqueous Nasal Inhalation Products for Droplet/Particle Size Distribution: an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - William H. Doub; Julie M. Suman; Mark Copley; Adrian P. Goodey; Sana Hosseini; Jolyon P. Mitchell (AAPS PharmSciTech, 2023)
Although nasal inhalation products are becoming more and more important for the delivery of medicines, characterization of these products for quality control and assessment of bioequivalence is complicated. Most of the problems encountered are associated with the assessment of aerodynamic droplet/particle size distribution (APSD). The droplets produced by the various nasal devices are large, and for suspension products, individual droplets may contain multiple drug particles or none at all. Assessment of suspension products is further complicated by the presence of solid excipient particles. These complications make it imperative that the limitations of the instruments used for characterization as well as the underlying assumptions that govern the interpretation of data produced by these instruments are understood. In this paper, we describe various methodologies used to assess APSD for nasal inhalation products and discuss proper use, limitations, and new methodologies on the horizon.

Defensive response of evolutionarily naïve Pinus sylvestris to the mountain pine beetle fungal associate Grosmannia clavigera in comparison to Pinus ponderosa - Kevin D. Chase; Kathryn J. Rynders; Mitchell P. Maddox; Brian H. Aukema (Forest Ecology and Management, 2023)

Articles You Might Have Missed - Christopher P. Mitchell; Elizabeth G. Shanahan (Journal of Medical Toxicology, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Design from recycling: Overcoming barriers in regranulate use in a circular economy - Martina Seier; Julia Roitner; Vasiliki-Maria Archodoulaki; Mitchell P. Jones (Resources, Conservation and Recycling, 2023)

A pair of cadmium-exposed zebrafish affect social behavior of the un-exposed majority - Delia S. Shelton; Zoe M. Dinges; Anuj Khemka; Delawrence J. Sykes; Piyumika S. Suriyampola; Dolores E.P. Shelton; Ploypenmas Boyd; Jeffrey R. Kelly; Myra Bower; Halima Amro; Stephen P. Glaholt; Mitchell B. Latta; et al. (Environmental Toxicology and Pharmacology, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

Recycling of polyethylene: Tribology assessment - Harsha Raghuram; Julia Roitner; Mitchell P. Jones; Vasiliki-Maria Archodoulaki (Resources, Conservation and Recycling, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Experimental and Numerical Investigation into the Fracture Patterns Induced by Blast-Loading Under Unconfined and Confined Conditions - T. R. Mitchell; Z. Wang; M. Araos; C. R. Leonardi; P. R. Gefken; I. A. Onederra (Rock Mechanics and Rock Engineering, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Mapping connectivity and conservation opportunity on agricultural lands across the conterminous United States - Justin P. Suraci; Caitlin E. Littlefield; Charlie C. Nicholson; Mitchell C. Hunter; Ann Sorensen; Brett G. Dickson (Biological Conservation, 2023)

Neural manifold analysis of brain circuit dynamics in health and disease - Rufus Mitchell-Heggs; Seigfred Prado; Giuseppe P. Gava; Mary Ann Go; Simon R. Schultz (Journal of Computational Neuroscience, 2023)
Recent developments in experimental neuroscience make it possible to simultaneously record the activity of thousands of neurons. However, the development of analysis approaches for such large-scale neural recordings have been slower than those applicable to single-cell experiments. One approach that has gained recent popularity is neural manifold learning. This approach takes advantage of the fact that often, even though neural datasets may be very high dimensional, the dynamics of neural activity tends to traverse a much lower-dimensional space. The topological structures formed by these low-dimensional neural subspaces are referred to as “neural manifolds”, and may potentially provide insight linking neural circuit dynamics with cognitive function and behavioral performance. In this paper we review a number of linear and non-linear approaches to neural manifold learning, including principal component analysis (PCA), multi-dimensional scaling (MDS), Isomap, locally linear embedding (LLE), Laplacian eigenmaps (LEM), t-SNE, and uniform manifold approximation and projection (UMAP). We outline these methods under a common mathematical nomenclature, and compare their advantages and disadvantages with respect to their use for neural data analysis. We apply them to a number of datasets from published literature, comparing the manifolds that result from their application to hippocampal place cells, motor cortical neurons during a reaching task, and prefrontal cortical neurons during a multi-behavior task. We find that in many circumstances linear algorithms produce similar results to non-linear methods, although in particular cases where the behavioral complexity is greater, non-linear methods tend to find lower-dimensional manifolds, at the possible expense of interpretability. We demonstrate that these methods are applicable to the study of neurological disorders through simulation of a mouse model of Alzheimer’s Disease, and speculate that neural manifold analysis may help us to understand the circuit-level consequences of molecular and cellular neuropathology.

Minimal adaptation of the molecular regulators of mitochondrial dynamics in response to unilateral limb immobilisation and retraining in middle-aged men - Chantal A. Pileggi; Christopher P. Hedges; Randall F. D’Souza; Brenan R. Durainayagam; Nina Zeng; Vandre C. Figueiredo; Anthony J. R. Hickey; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Mainstreaming germline genetic testing for patients with pancreatic cancer increases uptake - Mitchell L. Ramsey; Jewel Tomlinson; Rachel Pearlman; Laith Abushahin; Amber Aeilts; Hui-Zi Chen; Yan Chen; Ashley Compton; Rifat Elkhatib; Levi Geiger; John Hays; Joanne Jeter; et al. (Familial Cancer, 2023)

Breeding oat for resistance to the crown rust pathogen Puccinia coronata f. sp. avenae: achievements and prospects - R. F. Park; W. H. P. Boshoff; A. L. Cabral; J. Chong; J. A. Martinelli; M. S. McMullen; J. W. Mitchell Fetch; E. Paczos-Grzęda; E. Prats; J. Roake; S. Sowa; L. Ziems; et al. (Theoretical and Applied Genetics, 2022)
Crown rust, caused by Puccinia coronata f. sp. avenae ( Pca ), is a significant impediment to global oat production. Some 98 alleles at 92 loci conferring resistance to Pca in Avena have been designated; however, allelic relationships and chromosomal locations of many of these are unknown. Long-term monitoring of Pca in Australia, North America and elsewhere has shown that it is highly variable even in the absence of sexual recombination, likely due to large pathogen populations that cycle between wild oat communities and oat crops. Efforts to develop cultivars with genetic resistance to Pca began in the 1950s. Based almost solely on all all-stage resistance, this has had temporary benefits but very limited success. The inability to eradicate wild oats, and their common occurrence in many oat growing regions, means that future strategies to control Pca must be based on the assumption of a large and variable prevailing pathogen population with high evolutionary potential, even if cultivars with durable resistance are deployed and grown widely. The presence of minor gene, additive APR to Pca in hexaploid oat germplasm opens the possibility of pyramiding several such genes to give high levels of resistance. The recent availability of reference genomes for diploid and hexaploid oat will undoubtedly accelerate efforts to discover, characterise and develop high throughput diagnostic markers to introgress and pyramid resistance to Pca in high yielding adapted oat germplasm.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Quality of Life Changes Following the Onset of Cerebellar Ataxia: Symptoms and Concerns Self-reported by Ataxia Patients and Informants - Michelle R. Joyce; Prianca A. Nadkarni; Sharif I. Kronemer; Michael J. Margron; Mitchell B. Slapik; Owen P. Morgan; Liana S. Rosenthal; Chiadi U. Onyike; Cherie L. Marvel (The Cerebellum, 2022)

Prostacyclin (PGI2) scaffolds in medicinal chemistry: current and emerging drugs - Ghina’a I. Abu Deiab; Mitchell P. Croatt (Medicinal Chemistry Research, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Behavior of potentially toxic elements from stoker-boiler fly ash in Interior Alaska: paired batch leaching and solid-phase characterization - Kyle P. Milke; Kiana L. Mitchell; Sarah M. Hayes; Carlin J. Green; Jennifer J. Guerard (Environmental Science and Pollution Research, 2022)
Despite significant investigation of fly ash spills and mineralogical controls on the release of potentially toxic elements (PTEs) from fly ash, interactions with the surficial environment remain relatively poorly understood. We conducted 90-day batch leaching studies with paired analysis of supernatant and solid-phase mineralogy to assess the elemental release and transformation of fly ash upon reaction with aquatic media (18 MΩ cm −1 water and simulated rainwater). The fly ash in this study, collected from the University of Alaska Fairbanks stoker-boiler power plant, is high in unburned carbon (~20% LOI) and highly enriched in several PTEs relative to the upper continental crust. Supernatant concentrations of oxyanion-forming elements (e.g., As, Se, Mo, Sb) remained relatively low and constant, suggesting equilibrium with the solid phase, possibly ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 •26H 2 O], which is known to incorporate and sorb oxyanion-forming PTEs and was identified by X-ray diffraction. Synthetic precipitation leaching procedure (SPLP) results failed to capture important temporal trends. Lead and Ba supernatant concentrations consistently exceeded drinking water standards, as well as others upon exposure to simulated physiological solutions. Seven-day experiments with dissolved organic matter-isolate solutions indicated that for certain elements, liberation was influenced by carbon concentration and/or the identity of the isolate. Overall, this paired approach can serve as a model for future studies, bridging existing gaps between batch leaching and single-element mineralogical, sorption, or speciation studies.

Sexual assault and white matter hyperintensities among midlife women - Rebecca C. Thurston; Karen P. Jakubowski; Minjie Wu; Howard J. Aizenstein; Yuefang Chang; Carol A. Derby; Karestan C. Koenen; Emma Barinas-Mitchell; Pauline M. Maki (Brain Imaging and Behavior, 2022)

Drivers of fine‐scale diurnal space use by a coral‐reef mesopredatory fish - Alastair R. Harborne; David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Drew W. Butkowski; Manuel González‐Rivero (Journal of Fish Biology, 2022)
The habitat preferences of many reef fishes are well established, but the use of space within these habitats by non‐site‐attached species is poorly studied. The authors examined the space use of a functionally important mesopredator, graysby ( Cephalopholis cruentata ), on six patch reefs in the Florida Keys. A 1 m 2 ‐scale grid was constructed on each reef and 16 individual C. cruentata were tracked diurnally in situ to identify space use. At the patch reef scale, larger C. cruentata were more active and had larger observed home ranges, although home ranges were also affected by fish density and the abundances of prey and predators. The total time in each 1 m 2 grid cell was regressed against a range of fine‐scale biotic variables, including multiple variables derived from structure‐from‐motion three‐dimensional digital reconstructions of each reef. Nonetheless, time in grid cells (preferred microhabitats) was only significantly positively correlated with the height of carbonate structures, likely because the cavities they enclose are particularly suitable for predator avoidance, resting and ambushing prey. The ongoing flattening of reefs in the region caused by negative carbonate budgets is thus likely to have significant effects on the abundance and space use of C. cruentata . In addition to examining spatial patterns, we analysed C. cruentata waiting times in each grid cell before moving. These times were best approximated by a truncated power‐law (heavy‐tailed) distribution, indicating a “bursty” pattern of relatively long periods of inactivity interspersed with multiple periods of activity. Such a pattern has previously been identified in a range of temperate ambush predators, and the authors extend this move‐wait behaviour, which may optimize foraging success, to a reef fish for the first time. Understanding how C. cruentata uses space and time is critical to fully identify their functional role and better predict the implications of fishing and loss of reef structure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate drivers of adult insect activity are conditioned by life history traits - Michael W. Belitz; Vijay Barve; Joshua R. Doby; Maggie M. Hantak; Elise A. Larsen; Daijiang Li; Jessica A. Oswald; Neeka Sewnath; Mitchell Walters; Narayani Barve; Kamala Earl; Nicholas Gardner; et al. (Ecology Letters, 2021)
Insect phenological lability is key for determining which species will adapt under environmental change. However, little is known about when adult insect activity terminates and overall activity duration. We used community‐science and museum specimen data to investigate the effects of climate and urbanisation on timing of adult insect activity for 101 species varying in life history traits. We found detritivores and species with aquatic larval stages extend activity periods most rapidly in response to increasing regional temperature. Conversely, species with subterranean larval stages have relatively constant durations regardless of regional temperature. Species extended their period of adult activity similarly in warmer conditions regardless of voltinism classification. Longer adult durations may represent a general response to warming, but voltinism data in subtropical environments are likely underreported. This effort provides a framework to address the drivers of adult insect phenology at continental scales and a basis for predicting species response to environmental change.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Molecular Dynamics Simulations and Experimental Results Provide Insight into Clinical Performance Differences between Sandimmune® and Neoral® Lipid-Based Formulations - Dallas B. Warren; Shadabul Haque; Mitchell P. McInerney; Karen M. Corbett; Endri Kastrati; Leigh Ford; Hywel D. Williams; Vincent Jannin; Hassan Benameur; Christopher J.H. Porter; David K. Chalmers; Colin W. Pouton (Pharmaceutical Research, 2021)

Longleaf Pine ( Pinus palustris Mill.) Branch Pruning by Prescribed Fire - John P McGuire; John S Kush; J Morgan Varner; Dwight K Lauer; J Ryan Mitchell (Forest Science, 2021)
Efforts to restore longleaf pine (Pinus palustris Mill.) in the southeastern US require substantial artificial regeneration. Once established, important questions remain about when to introduce fire. We investigated the impact of initial planting density on tree branching and how prescribed fire might interact with tree architecture and survival. A particular focus was on how prescribed fires could “prune” lower branches. Lower density plantings (897 trees ha−1) had more and larger live lower branches than higher density plantings (2,243 trees ha−1). Fire was effective in pruning lower branches regardless of season burned, but fire in the growing season was more effective at pruning. Branches up to a height of 1.5 to 2 m were killed by fire. Fire applied in August caused greater damage with more needles scorched and/or consumed and more stem char. Prescribed fire did not impact longleaf pine tree survival. In general, fire applied to longleaf pine facilitated pruning lower branches that affect long-term wood quality, an additional argument for its utility in restoration and management of these ecosystems.

How can LCA include prospective elements to assess emerging technologies and system transitions? The 76th LCA Discussion Forum on Life Cycle Assessment, 19 November 2020 - Lugas Raka Adrianto; Mitchell K. van der Hulst; Janot P. Tokaya; Rickard Arvidsson; Carlos F. Blanco; Carla Caldeira; Gonzalo Guillén-Gonsálbez; Serenella Sala; Bernhard Steubing; Matthias Buyle; Mohamad Kaddoura; Nicolas H. Navarre; et al. (The International Journal of Life Cycle Assessment, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Environmental nitrate impacts foraging and agonistic behaviours of invasive non-native crayfish (Pacifastacus leniusculus and Faxonius virilis) - Joanna James; John R. Thomas; Alberto Maceda-Veiga; Robbie Mitchell; Ian P. Vaughan; Jo Cable (Hydrobiologia, 2021)

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

Neuropsychiatric Symptoms as a Reliable Phenomenology of Cerebellar Ataxia - Sharif I. Kronemer; Mitchell B. Slapik; Jessica R. Pietrowski; Michael J. Margron; Owen P. Morgan; Catherine C. Bakker; Liana S. Rosenthal; Chiadi U. Onyike; Cherie L. Marvel (The Cerebellum, 2021)

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Preclinical and Clinical Evidence for the Involvement of Sphingosine 1-Phosphate Signaling in the Pathophysiology of Vascular Cognitive Impairment - Xin Ying Chua; Leona T. Y. Ho; Ping Xiang; Wee Siong Chew; Brenda Wan Shing Lam; Christopher P. Chen; Wei-Yi Ong; Mitchell K. P. Lai; Deron R. Herr (NeuroMolecular Medicine, 2021)

Uniparental isodisomy of chromosome 2 causing MRPL44-related multisystem mitochondrial disease - Alejandro Horga; Andreea Manole; Alice L. Mitchell; Enrico Bugiardini; Iain P. Hargreaves; Walied Mowafi; Conceição Bettencourt; Emma L. Blakely; Langping He; James M. Polke; Catherine E. Woodward; Ilaria Dalla Rosa; et al. (Molecular Biology Reports, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

Correction to: Drying microclimates threaten persistence of natural and translocated populations of threatened frogs - Emily P. Hoffmann; Kim Williams; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2021)

Drying microclimates threaten persistence of natural and translocated populations of threatened frogs - Emily P. Hoffmann; Kim Williams; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2021)
Defining species habitat requirements is essential for effective conservation management through revealing agents of population decline and identifying critical habitat for conservation actions, such as translocations. Here we studied the habitat-associations of two threatened terrestrial-breeding frog species from southwestern Australia, Geocrinia alba and Geocrinia vitellina , to investigate if fine-scale habitat variables explain why populations occur in discrete patches, why G. alba is declining, and why translocation attempts have had mixed outcomes. We compared habitat variables at sites where the species are present, to variables at immediately adjacent sites where frogs are absent, and at sites where G. alba is locally extinct. Dry season soil moisture was the most important predictor of frog abundance for both species, and explained why G. alba had become extinct from some areas. Sites where G. alba were present were also positively associated with moss cover, and negatively with bare ground and soil conductivity. Modelling frog abundance based exclusively on dry season soil moisture predicted recent translocation successes with high accuracy. Hence, considering dry season soil moisture when selecting future translocation sites should increase the probability of population establishment. We propose that a regional drying trend is the most likely cause for G. alba declines and that both species are at risk of further habitat and range contraction due to further projected regional declines in rainfall and groundwater levels. More broadly, our study highlights that conservation areas in drying climates may not provide adequate protection and may require interventions to preserve critical habitat.

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

Evaluating a Rapid Field Assessment System for Anticoagulant Rodenticide Exposure of Raptors - Ariana J. Dickson; James R. Belthoff; Kristen A. Mitchell; Brian W. Smith; Zachary P. Wallace; Matthew J. Stuber; Michael J. Lockhart; Barnett A. Rattner; Todd E. Katzner (Archives of Environmental Contamination and Toxicology, 2020)

A Phase I Study to Evaluate Two Doses of Wharton’s Jelly-Derived Mesenchymal Stromal Cells for the Treatment of De Novo High-Risk or Steroid-Refractory Acute Graft Versus Host Disease - Rupal P. Soder; Buddhadeb Dawn; Mark L. Weiss; Neil Dunavin; Scott Weir; James Mitchell; Meizhang Li; Leyla Shune; Anurag K. Singh; Siddhartha Ganguly; Marc Morrison; Haitham Abdelhakim; et al. (Stem Cell Reviews and Reports, 2020)

Addressing the Need for Controls on Particle Bounce and Re-entrainment in the Cascade Impactor and for the Mitigation of Electrostatic Charge for Aerodynamic Particle Size Assessment of Orally Inhaled Products: an Assessment by the International Consortium on Regulation and Science (IPAC-RS) - William Doub; Stephen Stein; Jolyon Mitchell; Adrian P. Goodey (AAPS PharmSciTech, 2020)

Evaluation of Structured and Unstructured Models for Application in Operational Ocean Forecasting in Nearshore Waters - Shannon Nudds; Youyu Lu; Simon Higginson; Susan P. Haigh; Jean-Philippe Paquin; Mitchell O’Flaherty-Sproul; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Gregory C. Smith; Natacha B. Bernier; Phillip MacAulay; et al. (Journal of Marine Science and Engineering, 2020)
The oceanography sub-initiative of Canada’s Oceans Protection Plan was tasked to develop high-resolution nearshore ocean models for enhanced marine safety and emergency response, fitting into the multi-scale, multi-level nested operational ocean forecasting systems. For decision making on eventual 24/7 operational support, two ocean models (a structured grid model, NEMO (Nucleus for European Modelling of the Ocean); and an unstructured grid model, FVCOM (Finite Volume Coastal Ocean Model), were evaluated. The evaluation process includes the selection of the study area, the requirements for model setup, and the evaluation metrics. The chosen study area, Saint John Harbour in the Bay of Fundy, features strong tides, significant river runoff and a narrow tidal-river channel. Both models were configured with the same sources of bathymetry and forcing data. FVCOM achieved 50-100 m horizontal resolution in the inner harbour and included wetting/drying. NEMO achieved 100 m resolution in the harbour with a three-level one-way nesting configuration. Statistical metrics showed that one-year simulations with both models achieved comparable accuracies against the observed tidal and non-tidal water levels and currents, temperature and salinity, and the trajectories of surface drifters, but the computational cost of FVCOM was significantly less than that of NEMO.

O-GlcNAcylation as a Therapeutic Target for Alzheimer’s Disease - Jinsu Park; Mitchell K. P. Lai; Thiruma V. Arumugam; Dong-Gyu Jo (NeuroMolecular Medicine, 2020)

Using ancient DNA to quantify losses of genetic and species diversity in seabirds: a case study of Pterodroma petrels from a Pacific island - Anicee J. Lombal; Alexander T. Salis; Kieren J. Mitchell; Alan J. D. Tennyson; Lara D. Shepherd; Trevor H. Worthy; Eric J. Woehler; Jeremy J. Austin; Christopher P. Burridge (Biodiversity and Conservation, 2020)

Colonies of the fungus Aspergillus niger are highly differentiated to adapt to local carbon source variation - Paul Daly; Mao Peng; Hugh D. Mitchell; Young‐Mo Kim; Charles Ansong; Heather Brewer; Peter de Gijsel; Mary S. Lipton; Lye Meng Markillie; Carrie D. Nicora; Galya Orr; Ad Wiebenga; et al. (Environmental Microbiology, 2020)
Summary Saprobic fungi, such as Aspergillus niger , grow as colonies consisting of a network of branching and fusing hyphae that are often considered to be relatively uniform entities in which nutrients can freely move through the hyphae. In nature, different parts of a colony are often exposed to different nutrients. We have investigated, using a multi‐omics approach, adaptation of A. niger colonies to spatially separated and compositionally different plant biomass substrates. This demonstrated a high level of intra‐colony differentiation, which closely matched the locally available substrate. The part of the colony exposed to pectin‐rich sugar beet pulp and to xylan‐rich wheat bran showed high pectinolytic and high xylanolytic transcript and protein levels respectively. This study therefore exemplifies the high ability of fungal colonies to differentiate and adapt to local conditions, ensuring efficient use of the available nutrients, rather than maintaining a uniform physiology throughout the colony.

NMR and computational methods for molecular resolution of allosteric pathways in enzyme complexes - Kyle W. East; Erin Skeens; Jennifer Y. Cui; Helen B. Belato; Brandon Mitchell; Rohaine Hsu; Victor S. Batista; Giulia Palermo; George P. Lisi (Biophysical Reviews, 2020)

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

Ingestion and Absorption of Eucalypt Monoterpenes in the Specialist Feeder, the Koala (Phascolarctos cinereus) - Caroline Marschner; Mark B. Krockenberger; Damien P. Higgins; Christopher Mitchell; Ben D. Moore (Journal of Chemical Ecology, 2019)

Methane emissions from abandoned coal and oil and gas developments in New Brunswick and Nova Scotia - James P. Williams; David Risk; Alexander Marshall; Nick Nickerson; Alexandra Martell; Chance Creelman; Mitchell Grace; Grant Wach (Environmental Monitoring and Assessment, 2019)

Towards an African Light Source - Simon H. Connell; Sekazi K. Mtingwa; Tabbetha Dobbins; Nkem Khumbah; Brian Masara; Edward P. Mitchell; Lawrence Norris; Prosper Ngabonziza; Tshepo Ntsoane; Herman Winick (Biophysical Reviews, 2019)

The role of simulated spring water stress in interactions between eastern larch and larch casebearer - Samuel F. Ward; Aubree M. Kees; Mitchell P. Maddox; Rebecca A. Montgomery; Brian H. Aukema (Arthropod-Plant Interactions, 2019)

Submarine giant pumice: a window into the shallow conduit dynamics of a recent silicic eruption - Samuel J. Mitchell; Bruce F. Houghton; Rebecca J. Carey; Michael Manga; Kristen E. Fauria; Max P. Jones; S. Adam Soule; Chris E. Conway; Zihan Wei; Thomas Giachetti (Bulletin of Volcanology, 2019)
Meter-scale vesicular blocks, termed “giant pumice,” are characteristic primary products of many subaqueous silicic eruptions. The size of giant pumices allows us to describe meter-scale variations in textures and geochemistry with implications for shearing processes, ascent dynamics, and thermal histories within submarine conduits prior to eruption. The submarine eruption of Havre volcano, Kermadec Arc, in 2012, produced at least 0.1 km 3 of rhyolitic giant pumice from a single 900-m-deep vent, with blocks up to 10 m in size transported to at least 6 km from source. We sampled and analyzed 29 giant pumices from the 2012 Havre eruption. Geochemical analyses of whole rock and matrix glass show no evidence for geochemical heterogeneities in parental magma; any textural variations can be attributed to crystallization of phenocrysts and microlites, and degassing. Extensive growth of microlites occurred near conduit walls where magma was then mingled with ascending microlite-poor, low viscosity rhyolite. Meter- to micron-scale textural analyses of giant pumices identify diversity throughout an individual block and between the exteriors of individual blocks. We identify evidence for post-disruption vesicle growth during pumice ascent in the water column above the submarine vent. A 2D cumulative strain model with a flared, shallow conduit may explain observed vesicularity contrasts (elongate tube vesicles vs spherical vesicles). Low vesicle number densities in these pumices from this high-intensity silicic eruption demonstrate the effect of hydrostatic pressure above a deep submarine vent in suppressing rapid late-stage bubble nucleation and inhibiting explosive fragmentation in the shallow conduit.

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Determination of Passive Dry Powder Inhaler Aerodynamic Particle Size Distribution by Multi-Stage Cascade Impactor: International Pharmaceutical Aerosol Consortium on Regulation & Science (IPAC-RS) Recommendations to Support Both Product Quality Control and Clinical Programs - Jolyon P. Mitchell; Stephen W. Stein; William Doub; Adrian P. Goodey; J. David Christopher; Rajni B. Patel; Terrence P. Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2019)

Treading Water: Tools to Help US Coastal Communities Plan for Sea Level Rise Impacts - Emily A. Smith; William Sweet; Molly Mitchell; Ricardo Domingues; Christopher P. Weaver; Molly Baringer; Gustavo Goni; John Haines; J. Derek Loftis; John Boon; David Malmquist (Frontiers in Marine Science, 2019)

Time to revisit? A predator’s previous successes and failures in prey capture determine its return time to patches - S. Vijayan; J. K. Lee; J. Balaban-Feld; W. A. Mitchell; B. P. Kotler; M. L. Rosenzweig; T. T. Lotan; Z. Abramsky (Oecologia, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Woody vegetation dynamics in the tropical and subtropical Andes from 2001 to 2014: Satellite image interpretation and expert validation - T. Mitchell Aide; H. Ricardo Grau; Jordan Graesser; Maria Jose Andrade‐Nuñez; Ezequiel Aráoz; Ana P. Barros; Marconi Campos‐Cerqueira; Eulogio Chacon‐Moreno; Francisco Cuesta; Raul Espinoza; Manuel Peralvo; Molly H. Polk; et al. (Global Change Biology, 2019)
The interactions between climate and land‐use change are dictating the distribution of flora and fauna and reshuffling biotic community composition around the world. Tropical mountains are particularly sensitive because they often have a high human population density, a long history of agriculture, range‐restricted species, and high‐beta diversity due to a steep elevation gradient. Here we evaluated the change in distribution of woody vegetation in the tropical Andes of South America for the period 2001–2014. For the analyses we created annual land‐cover/land‐use maps using MODIS satellite data at 250 m pixel resolution, calculated the cover of woody vegetation (trees and shrubs) in 9,274 hexagons of 115.47 km 2 , and then determined if there was a statistically significant ( p n = 479) lost forests and 63.4% ( n = 829) gained forests. We estimated an overall net gain of ~500,000 ha in woody vegetation. Forest loss dominated the 1,000–1,499 m elevation zone and forest gain dominated above 1,500 m. The most important transitions were forest loss at lower elevations for pastures and croplands, forest gain in abandoned pastures and cropland in mid‐elevation areas, and shrub encroachment into highland grasslands. Expert validation confirmed the observed trends, but some areas of apparent forest gain were associated with new shade coffee, pine, or eucalypt plantations. In addition, after controlling for elevation and country, forest gain was associated with a decline in the rural population. Although we document an overall gain in forest cover, the recent reversal of forest gains in Colombia demonstrates that these coupled natural‐human systems are highly dynamic and there is an urgent need of a regional real‐time land‐use, biodiversity, and ecosystem services monitoring network.

State-dependent foraging among social fish in a risky environment - Jesse Balaban-Feld; William A. Mitchell; Burt P. Kotler; Sundararaj Vijayan; Lotan T. Tov Elem; Zvika Abramsky (Oecologia, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Measurement of Aerodynamic Particle Size Distribution of Orally Inhaled Products by Cascade Impactor: How to Let the Product Specification Drive the Quality Requirements of the Cascade Impactor - Daryl L. Roberts; Jolyon P. Mitchell (AAPS PharmSciTech, 2019)

Shark depredation in commercial and recreational fisheries - J. D. Mitchell; D. L. McLean; S. P. Collin; T. J. Langlois (Reviews in Fish Biology and Fisheries, 2018)

Repeatability of central corneal thickness measurements of donor corneas in preservation chamber using Fourier-domain anterior segment optical coherence tomography - Abhinav Golla; Li Wang; Caleb Morris; Mitchell P. Weikert; Sumitra S. Khandelwal (Cell and Tissue Banking, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Evaluation of Nasal Inlet Ports Having Simplified Geometry for the Pharmacopeial Assessment of Mass Fraction of Dose Likely to Penetrate Beyond the Nasopharynx: a Preliminary Investigation - Gerallt Williams; Chris Blatchford; Jolyon P. Mitchell (AAPS PharmSciTech, 2018)

Inter-Annual Precipitation Variability Decreases Switchgrass Productivity from Arid to Mesic Environments - Lara G. Reichmann; Harold P. Collins; Virginia L. Jin; Mari-Vaughn V. Johnson; Jim R. Kiniry; Robert B. Mitchell; H. Wayne Polley; Philip A. Fay (BioEnergy Research, 2018)

The putative leucine sensor Sestrin2 is hyperphosphorylated by acute resistance exercise but not protein ingestion in human skeletal muscle - Nina Zeng; Randall F. D’Souza; Brie Sorrenson; Troy L. Merry; Matthew P. G. Barnett; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2018)

A pharmacokinetic model for amiodarone in infants developed from an opportunistic sampling trial and published literature data - Samantha H. Dallefeld; Andrew M. Atz; Ram Yogev; Janice E. Sullivan; Amira Al-Uzri; Susan R. Mendley; Matthew Laughon; Christoph P. Hornik; Chiara Melloni; Barrie Harper; Andrew Lewandowski; Jeff Mitchell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Influence of predation risk on individual spatial positioning and willingness to leave a safe refuge in a social benthic fish - Jesse Balaban-Feld; William A. Mitchell; Burt P. Kotler; Sundararaj Vijayan; Lotan T. Tov Elem; Zvika Abramsky (Behavioral Ecology and Sociobiology, 2018)

Colletotrichum species associated with pre-and post-harvest diseases of avocado and mango in eastern Australia - F. R. Giblin; Y. P. Tan; R. Mitchell; L. M. Coates; J. A. G. Irwin; R. G. Shivas (Australasian Plant Pathology, 2018)

Ionophore and Biometal Modulation of P-glycoprotein Expression and Function in Human Brain Microvascular Endothelial Cells - Mitchell P. McInerney; Irene Volitakis; Ashley I. Bush; William A. Banks; Jennifer L. Short; Joseph A. Nicolazzo (Pharmaceutical Research, 2018)

Global environmental change effects on plant community composition trajectories depend upon management legacies - Michael P. Perring; Markus Bernhardt‐Römermann; Lander Baeten; Gabriele Midolo; Haben Blondeel; Leen Depauw; Dries Landuyt; Sybryn L. Maes; Emiel De Lombaerde; Maria Mercedes Carón; Mark Vellend; Jörg Brunet; et al. (Global Change Biology, 2018)
The contemporary state of functional traits and species richness in plant communities depends on legacy effects of past disturbances. Whether temporal responses of community properties to current environmental changes are altered by such legacies is, however, unknown. We expect global environmental changes to interact with land‐use legacies given different community trajectories initiated by prior management, and subsequent responses to altered resources and conditions. We tested this expectation for species richness and functional traits using 1814 survey‐resurvey plot pairs of understorey communities from 40 European temperate forest datasets, syntheses of management transitions since the year 1800, and a trait database. We also examined how plant community indicators of resources and conditions changed in response to management legacies and environmental change. Community trajectories were clearly influenced by interactions between management legacies from over 200 years ago and environmental change. Importantly, higher rates of nitrogen deposition led to increased species richness and plant height in forests managed less intensively in 1800 (i.e., high forests), and to decreases in forests with a more intensive historical management in 1800 (i.e., coppiced forests). There was evidence that these declines in community variables in formerly coppiced forests were ameliorated by increased rates of temperature change between surveys. Responses were generally apparent regardless of sites’ contemporary management classifications, although sometimes the management transition itself, rather than historic or contemporary management types, better explained understorey responses. Main effects of environmental change were rare, although higher rates of precipitation change increased plant height, accompanied by increases in fertility indicator values. Analysis of indicator values suggested the importance of directly characterising resources and conditions to better understand legacy and environmental change effects. Accounting for legacies of past disturbance can reconcile contradictory literature results and appears crucial to anticipating future responses to global environmental change.

Species’ traits do not converge on optimum values in preferred habitats - Rachel M. Mitchell; Justin P. Wright; Greg M. Ames (Oecologia, 2018)

Challenges and opportunities for managing aquatic mercury pollution in altered landscapes - Heileen Hsu-Kim; Chris S. Eckley; Dario Achá; Xinbin Feng; Cynthia C. Gilmour; Sofi Jonsson; Carl P. J. Mitchell (Ambio, 2018)

Confirmation of a unique and genetically diverse ‘heritage’ strain of brook trout (Salvelinus fontinalis) in a remote Adirondack watershed - Spencer A. Bruce; Matthew P. Hare; Matthew W. Mitchell; Jeremy J. Wright (Conservation Genetics, 2018)

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Extreme weather‐year sequences have nonadditive effects on environmental nitrogen losses - Javed Iqbal; Magdalena Necpalova; Sotirios V. Archontoulis; Robert P. Anex; Marie Bourguignon; Daryl Herzmann; David C. Mitchell; John E. Sawyer; Qing Zhu; Michael J. Castellano (Global Change Biology, 2018)
The frequency and intensity of extreme weather years, characterized by abnormal precipitation and temperature, are increasing. In isolation, these years have disproportionately large effects on environmental N losses. However, the sequence of extreme weather years (e.g., wet–dry vs. dry–wet) may affect cumulative N losses. We calibrated and validated the DAYCENT ecosystem process model with a comprehensive set of biogeophysical measurements from a corn–soybean rotation managed at three N fertilizer inputs with and without a winter cover crop in Iowa, USA . Our objectives were to determine: (i) how 2‐year sequences of extreme weather affect 2‐year cumulative N losses across the crop rotation, and (ii) if N fertilizer management and the inclusion of a winter cover crop between corn and soybean mitigate the effect of extreme weather on N losses. Using historical weather (1951–2013), we created nine 2‐year scenarios with all possible combinations of the driest (“dry”), wettest (“wet”), and average (“normal”) weather years. We analyzed the effects of these scenarios following several consecutive years of relatively normal weather. Compared with the normal–normal 2‐year weather scenario, 2‐year extreme weather scenarios affected 2‐year cumulative NO 3 − leaching (range: −93 to +290%) more than N 2 O emissions (range: −49 to +18%). The 2‐year weather scenarios had nonadditive effects on N losses: compared with the normal–normal scenario, the dry–wet sequence decreased 2‐year cumulative N 2 O emissions while the wet–dry sequence increased 2‐year cumulative N 2 O emissions. Although dry weather decreased NO 3 − leaching and N 2 O emissions in isolation, 2‐year cumulative N losses from the wet–dry scenario were greater than the dry–wet scenario. Cover crops reduced the effects of extreme weather on NO 3 − leaching but had a lesser effect on N 2 O emissions. As the frequency of extreme weather is expected to increase, these data suggest that the sequence of interannual weather patterns can be used to develop short‐term mitigation strategies that manipulate N fertilizer and crop rotation to maximize crop N uptake while reducing environmental N losses.

Accumulation of Methylmercury in Invertebrates and Masked Shrews (Sorex cinereus) at an Upland Forest–Peatland Interface in Northern Minnesota, USA - Ilana Tavshunsky; Susan L. Eggert; Carl P. J. Mitchell (Bulletin of Environmental Contamination and Toxicology, 2017)

Discriminating Ability of Abbreviated Impactor Measurement Approach (AIM) to Detect Changes in Mass Median Aerodynamic Diameter (MMAD) of an Albuterol/Salbutamol pMDI Aerosol - J . David Christopher; Rajni B. Patel; Jolyon P. Mitchell; Terrence P. Tougas; Adrian P. Goodey; Jorge Quiroz; Patrik U. Andersson; Svetlana Lyapustina (AAPS PharmSciTech, 2017)

Development and Evaluation of a Family of Human Face and Upper Airway Models for the Laboratory Testing of Orally Inhaled Products - Mark W. Nagel; Jason A. Suggett; Dominic P. Coppolo; Jolyon P. Mitchell (AAPS PharmSciTech, 2017)

Pre-operative Screening and Manual Drilling Strategies to Reduce the Risk of Thermal Injury During Minimally Invasive Cochlear Implantation Surgery - Neal P. Dillon; Loris Fichera; Kyle Kesler; M. Geraldine Zuniga; Jason E. Mitchell; Robert J. Webster; Robert F. Labadie (Annals of Biomedical Engineering, 2017)

Neurovascular Alterations in Alzheimer’s Disease: Transporter Expression Profiles and CNS Drug Access - Mitchell P. McInerney; Jennifer L. Short; Joseph A. Nicolazzo (The AAPS Journal, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Metastatic melanoma moves on: translational science in the era of personalized medicine - Mitchell P. Levesque; Phil F. Cheng; Marieke I.G. Raaijmakers; Annalisa Saltari; Reinhard Dummer (Cancer and Metastasis Reviews, 2017)

Odorant receptors and antennal lobe morphology offer a new approach to understanding olfaction in the Asian longhorned beetle - Robert F. Mitchell; Loyal P. Hall; Peter F. Reagel; Duane D. McKenna; Thomas C. Baker; John G. Hildebrand (Journal of Comparative Physiology A, 2017)

A Comparison of the Performance of Efficient Data Analysis Versus Fine Particle Dose as Metrics for the Quality Control of Aerodynamic Particle Size Distributions of Orally Inhaled Pharmaceuticals - Terrence P. Tougas; Adrian P. Goodey; Gareth Hardwell; Jolyon Mitchell; Svetlana Lyapustina (AAPS PharmSciTech, 2017)

A Multi-laboratory in Vitro Study to Compare Data from Abbreviated and Pharmacopeial Impactor Measurements for Orally Inhaled Products: a Report of the European Aerosol Group (EPAG) - Steven C. Nichols; Jolyon P. Mitchell; Dennis Sandell; Patrik U. Andersson; Manfred Fischer; Markus Howald; Roy Pengilley; Phillip Krüger (AAPS PharmSciTech, 2016)

Joint effects of nutrient addition and enemy exclusion on exotic plant success - Robert W. Heckman; Justin P. Wright; Charles E. Mitchell (Ecology, 2016)
Worldwide, ecosystems are increasingly dominated by exotic plant species, a shift hypothesized to result from numerous ecological factors. Two of these, increased resource availability and enemy release, may act in concert to increase exotic success in plant communities (Resource‐Enemy Release Hypothesis, R‐ ERH ). To test this, we manipulated the availability of soil nutrients and access of vertebrate herbivores, insect herbivores, and fungal pathogens to intact grassland communities containing both native and exotic species. Our results supported both conditions necessary for R‐ ERH . First, exotics were less damaged than natives, experiencing less foliar damage (insect herbivory and fungal disease) than native species, particularly in communities where soil nutrients were added. Second, fertilization increased foliar damage on native species, but not exotic species. As well as fulfilling both conditions for R‐ ERH , these results demonstrate the importance of considering the effects of resource availability when testing for enemy release. When both conditions are fulfilled, R‐ ERH predicts that increasing resource availability will increase exotic abundance only in the presence of enemies. Our results fully supported this prediction for vertebrate herbivores: fertilization increased exotic cover only in communities exposed to vertebrate herbivores. Additionally, the prediction was partially supported for insect herbivores and fungal pathogens, excluding these enemies reduced exotic cover as predicted, but inconsistent with R‐ ERH , this effect occurred only in unfertilized communities. These results highlight the need to consider the influence of multiple enemy guilds on community processes like exotic plant invasions. Moreover, this study experimentally demonstrates that resource availability and natural enemies can jointly influence exotic success in plant communities.

Opposing effects of perceptual versus working memory load on emotional distraction - Tamara P. Tavares; Kyle Logie; Derek G. V. Mitchell (Experimental Brain Research, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

Biological Effects of Naturally Occurring Sphingolipids, Uncommon Variants, and Their Analogs - Mitchell K. P. Lai; Wee Siong Chew; Federico Torta; Angad Rao; Greg L. Harris; Jerold Chun; Deron R. Herr (NeuroMolecular Medicine, 2016)

African American Patients’ Psychosocial Support Needs and Barriers to Treatment: Patient Needs Assessment - Maureen P. Davey; Brianna Bilkins; Guy Diamond; Alliric I. Willis; Edith P. Mitchell; Adam Davey; Faith M. Young (Journal of Cancer Education, 2016)

Clinically Relevant In Vitro Testing of Orally Inhaled Products—Bridging the Gap Between the Lab and the Patient - Jolyon P. Mitchell; Jason Suggett; Mark Nagel (AAPS PharmSciTech, 2016)

Last interglacial (MIS 5e) sea-level determined from a tectonically stable, far-field location, Eyre Peninsula, southern Australia - C. V. Murray-Wallace; A. P. Belperio; A. Dosseto; W. A. Nicholas; C. Mitchell; R. P. Bourman; S. M. Eggins; R. Grün (Australian Journal of Earth Sciences, 2016)

Differential migration and the link between winter latitude, timing of migration, and breeding in a songbird - Bradley K. Woodworth; Amy E. M. Newman; Sheela P. Turbek; Bryant C. Dossman; Keith A. Hobson; Leonard I. Wassenaar; Greg W. Mitchell; Nathaniel T. Wheelwright; D. Ryan Norris (Oecologia, 2016)

Dedicated Energy Crops and Crop Residues for Bioenergy Feedstocks in the Central and Eastern USA - R. B. Mitchell; M. R. Schmer; W. F. Anderson; V. Jin; K. S. Balkcom; J. Kiniry; A. Coffin; P. White (BioEnergy Research, 2016)
Dedicated energy crops and crop residues will meet herbaceous feedstock demands for the new bioeconomy in the Central and Eastern USA. Perennial warm-season grasses and corn stover are well-suited to the eastern half of the USA and provide opportunities for expanding agricultural operations in the region. A suite of warm-season grasses and associated management practices have been developed by researchers from the Agricultural Research Service of the US Department of Agriculture (USDA) and collaborators associated with USDA Regional Biomass Research Centers. Second generation biofuel feedstocks provide an opportunity to increase the production of transportation fuels from recently fixed plant carbon rather than from fossil fuels. Although there is no “one-size-fits-all” bioenergy feedstock, crop residues like corn ( Zea mays L.) stover are the most readily available bioenergy feedstocks. However, on marginally productive cropland, perennial grasses provide a feedstock supply while enhancing ecosystem services. Twenty-five years of research has demonstrated that perennial grasses like switchgrass ( Panicum virgatum L.) are profitable and environmentally sustainable on marginally productive cropland in the western Corn Belt and Southeastern USA.

An ecoclimatic framework for evaluating the resilience of vegetation to water deficit - Patrick J. Mitchell; Anthony P. O'Grady; Elizabeth A. Pinkard; Timothy J. Brodribb; Stefan K. Arndt; Chris J. Blackman; Remko A. Duursma; Rod J. Fensham; David W. Hilbert; Craig R. Nitschke; Jaymie Norris; Stephen H. Roxburgh; et al. (Global Change Biology, 2016)
The surge in global efforts to understand the causes and consequences of drought on forest ecosystems has tended to focus on specific impacts such as mortality. We propose an ecoclimatic framework that takes a broader view of the ecological relevance of water deficits, linking elements of exposure and resilience to cumulative impacts on a range of ecosystem processes. This ecoclimatic framework is underpinned by two hypotheses: (i) exposure to water deficit can be represented probabilistically and used to estimate exposure thresholds across different vegetation types or ecosystems; and (ii) the cumulative impact of a series of water deficit events is defined by attributes governing the resistance and recovery of the affected processes. We present case studies comprising Pinus edulis and Eucalyptus globulus , tree species with contrasting ecological strategies, which demonstrate how links between exposure and resilience can be examined within our proposed framework. These examples reveal how climatic thresholds can be defined along a continuum of vegetation functional responses to water deficit regimes. The strength of this framework lies in identifying climatic thresholds on vegetation function in the absence of more complete mechanistic understanding, thereby guiding the formulation, application and benchmarking of more detailed modelling.

Grass Invasion into Switchgrass Managed for Biomass Energy - R. B. Mitchell; K. P. Vogel (BioEnergy Research, 2016)

Altered relaxin family receptors RXFP1 and RXFP3 in the neocortex of depressed Alzheimer’s disease patients - Jasinda H. Lee; Shu Qing Koh; Simone Guadagna; Paul T. Francis; Margaret M. Esiri; Christopher P. Chen; Peter T.-H. Wong; Gavin S. Dawe; Mitchell K. P. Lai (Psychopharmacology, 2016)

A major QTL corresponding to the Rk locus for resistance to root-knot nematodes in cowpea (Vigna unguiculata L. Walp.) - Bao-Lam Huynh; William C. Matthews; Jeffrey D. Ehlers; Mitchell R. Lucas; Jansen R. P. Santos; Arsenio Ndeve; Timothy J. Close; Philip A. Roberts (Theoretical and Applied Genetics, 2016)

Rapid purging of genetic load in a metapopulation and consequences for range expansion in an invasive plant - Gina L. Marchini; Nena Cole Sherlock; Alisa P. Ramakrishnan; David M. Rosenthal; Mitchell B. Cruzan (Biological Invasions, 2016)

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Environment Has Little Effect on Biomass Biochemical Composition of Miscanthus × giganteus Across Soil Types, Nitrogen Fertilization, and Times of Harvest - Rebecca A. Arundale; Stefan Bauer; Fernanda B. Haffner; Valerie D. Mitchell; Thomas B. Voigt; Stephen P. Long (BioEnergy Research, 2015)

An improved diagnostic for summertime rainfall along the eastern seaboard of Australia - Mitchell T. Black; Todd P. Lane (International Journal of Climatology, 2015)
The eastern seaboard of Australia ( ESB ) is a unique climate entity. A region of complex topography bound by the coastline and the ridge of the Great Dividing Range, the ESB exhibits distinctly different rainfall patterns to the rest of southeastern Australia. As a large percentage of the Australian population resides along the ESB , understanding current and future rainfall variability in this region presents an important and difficult challenge. This challenge is compounded by the inability of most general circulation models to properly resolve the region. This study presents a diagnostic for characterizing the variability in summertime rainfall along the ESB . This simple yet effective East Coast Flow Index ( ECFI ) infers easterly geostrophic flow from the meridional pressure gradient along the ESB , and vertical circulation from the upper‐level ω field. The ECFI outperforms the common indices for drivers of rainfall variability, achieving statistically significant correlations with ESB summertime rainfall for a range of different timescales. The ECFI is shown to have great potential as a predictor for statistically downscaling rainfall along the ESB as (1) it provides a physical link between large‐scale forcings and local precipitation responses, (2) is capable of capturing multiyear variability and (3) is realistically represented by general circulation models. While the ECFI was designed for the summer months (December–February) it is still capable of performing well in the other seasons, especially spring (September–November).

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

Calcium and aluminum cycling in a temperate broadleaved deciduous forest of the eastern USA: relative impacts of tree species, canopy state, and flux type - Delphis F. Levia; Alexey N. Shiklomanov; John T. Van Stan; Carrie E. Scheick; Shreeram P. Inamdar; Myron J. Mitchell; Patrick J. McHale (Environmental Monitoring and Assessment, 2015)

Comparative analyses of clinical and environmental populations of C ryptococcus neoformans in B otswana - Yuan Chen; Anastasia P. Litvintseva; Aubrey E. Frazzitta; Miriam R. Haverkamp; Liuyang Wang; Charles Fang; Charles Muthoga; Thomas G. Mitchell; John R. Perfect (Molecular Ecology, 2015)
C ryptococcus neoformans var. grubii ( Cng ) is the most common cause of fungal meningitis, and its prevalence is highest in sub‐Saharan Africa. Patients become infected by inhaling airborne spores or desiccated yeast cells from the environment, where the fungus thrives in avian droppings, trees and soil. To investigate the prevalence and population structure of Cng in southern Africa, we analysed isolates from 77 environmental samples and 64 patients. We detected significant genetic diversity among isolates and strong evidence of geographic structure at the local level. High proportions of isolates with the rare MAT a allele were observed in both clinical and environmental isolates; however, the mating‐type alleles were unevenly distributed among different subpopulations. Nearly equal proportions of the MAT a and MAT α mating types were observed among all clinical isolates and in one environmental subpopulation from the eastern part of Botswana. As previously reported, there was evidence of both clonality and recombination in different geographic areas. These results provide a foundation for subsequent genomewide association studies to identify genes and genotypes linked to pathogenicity in humans.

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Pseudotachylyte and Fluid Alteration at Seismogenic Depths (Glacier Lakes and Granite Pass Faults, Central Sierra Nevada, USA) - Mitchell R. Prante; James P. Evans (Pure and Applied Geophysics, 2015)

Climatic and geographic relations of alpine tundra floras in western North America - George P. Malanson; Ashley B. Cheney; Mitchell Kinney (Alpine Botany, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Pollen‐based quantitative reconstructions of Holocene regional vegetation cover (plant‐functional types and land‐cover types) in Europe suitable for climate modelling - A.‐K. Trondman; M.‐J. Gaillard; F. Mazier; S. Sugita; R. Fyfe; A. B. Nielsen; C. Twiddle; P. Barratt; H. J. B. Birks; A. E. Bjune; L. Björkman; A. Broström; et al. (Global Change Biology, 2015)
We present quantitative reconstructions of regional vegetation cover in north‐western Europe, western Europe north of the Alps, and eastern Europe for five time windows in the Holocene [around 6k, 3k, 0.5k, 0.2k, and 0.05k calendar years before present ( bp )] at a 1° × 1° spatial scale with the objective of producing vegetation descriptions suitable for climate modelling. The REVEALS model was applied on 636 pollen records from lakes and bogs to reconstruct the past cover of 25 plant taxa grouped into 10 plant‐functional types and three land‐cover types [evergreen trees, summer‐green (deciduous) trees, and open land]. The model corrects for some of the biases in pollen percentages by using pollen productivity estimates and fall speeds of pollen, and by applying simple but robust models of pollen dispersal and deposition. The emerging patterns of tree migration and deforestation between 6k bp and modern time in the REVEALS estimates agree with our general understanding of the vegetation history of Europe based on pollen percentages. However, the degree of anthropogenic deforestation (i.e. cover of cultivated and grazing land) at 3k, 0.5k, and 0.2k bp is significantly higher than deduced from pollen percentages. This is also the case at 6k in some parts of Europe, in particular Britain and Ireland. Furthermore, the relationship between summer‐green and evergreen trees, and between individual tree taxa, differs significantly when expressed as pollen percentages or as REVEALS estimates of tree cover. For instance, when Pinus is dominant over Picea as pollen percentages, Picea is dominant over Pinus as REVEALS estimates. These differences play a major role in the reconstruction of European landscapes and for the study of land cover–climate interactions, biodiversity and human resources.

3D seismic analysis of complex faulting patterns above the Snapper Field, Gippsland Basin: implications for CO 2 storage - E. Swierczek; G. Backe; S. P. Holford; E. Tenthorey; A. Mitchell (Australian Journal of Earth Sciences, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Risks of large-scale use of systemic insecticides to ecosystem functioning and services - Madeleine Chagnon; David Kreutzweiser; Edward A.D. Mitchell; Christy A. Morrissey; Dominique A. Noome; Jeroen P. Van der Sluijs (Environmental Science and Pollution Research, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Mercury proxies and mercury dynamics in a forested watershed of the US Northeast - P. Vidon; W. Carleton; M. J. Mitchell (Environmental Monitoring and Assessment, 2014)

Developing Ways to Evaluate in the Laboratory How Inhalation Devices Will Be Used by Patients and Care-Givers: The Need for Clinically Appropriate Testing - Jolyon P. Mitchell; Jason A. Suggett (AAPS PharmSciTech, 2014)

Investigation of Dry Powder Inhaler (DPI) Resistance and Aerosol Dispersion Timing on Emitted Aerosol Aerodynamic Particle Sizing by Multistage Cascade Impactor when Sampled Volume Is Reduced from Compendial Value of 4 L - Hlack Mohammed; Jan Arp; Frank Chambers; Mark Copley; Volker Glaab; Mark Hammond; Derek Solomon; Kerry Bradford; Theresa Russell; Yvonne Sizer; Steven C. Nichols; Daryl L. Roberts; et al. (AAPS PharmSciTech, 2014)

Quantifying the impact of environmental variables upon catch per unit effort of the blue shark Prionace glauca in the western English Channel - J. D. Mitchell; K. J. Collins; P. I. Miller; L. A. Suberg (Journal of Fish Biology, 2014)
The effect of environmental variables on blue shark Prionace glauca catch per unit effort ( CPUE ) in a recreational fishery in the western English Channel, between June and September 1998–2011, was quantified using generalized additive models ( GAMs ). Sea surface temperature ( SST ) explained 1·4% of GAM deviance, and highest CPUE occurred at 16·7° C, reflecting the optimal thermal preferences of this species. Surface chlorophyll a concentration ( CHL ) significantly affected CPUE and caused 27·5% of GAM deviance. Additionally, increasing CHL led to rising CPUE , probably due to higher productivity supporting greater prey biomass. The density of shelf‐sea tidal mixing fronts explained 5% of GAM deviance, but was non‐significant, with increasing front density negatively affecting CPUE. Time‐lagged frontal density significantly affected CPUE, however, causing 12·6% of the deviance in a second GAM and displayed a positive correlation. This outcome suggested a delay between the evolution of frontal features and the subsequent accumulation of productivity and attraction of higher trophic level predators, such as P. glauca .

Cascading Effects of Climate Change on Forest Ecosystems: Biogeochemical Links Between Trees and Moose in the Northeast USA - L. M. Christenson; M. J. Mitchell; P. M. Groffman; G. M. Lovett (Ecosystems, 2014)

The role of scientific studies in building consensus in environmental decision making: a coral reef example - Amanda P. Rehr; Mitchell J. Small; Paul S. Fischbeck; Patricia Bradley; William S. Fisher (Environment Systems and Decisions, 2014)

When depth is no refuge: cumulative thermal stress increases with depth in Bocas del Toro, Panama - B. P. Neal; C. Condit; G. Liu; S. dos Santos; M. Kahru; B. G. Mitchell; D. I. Kline (Coral Reefs, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Activity of the plant-based repellent, TT-4302 against the ticks Amblyomma americanum, Dermacentor variabilis, Ixodes scapularis and Rhipicephalus sanguineus (Acari: Ixodidae) - B. W. Bissinger; J. P. Schmidt; J. J. Owens; S. M. Mitchell; M. K. Kennedy (Experimental and Applied Acarology, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Reproductive biology of wahoo, Acanthocybium solandri, off eastern Australia - Mitchell T. Zischke; Jessica H. Farley; Shane P. Griffiths; Ian R. Tibbetts (Reviews in Fish Biology and Fisheries, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Efficacy of novel sampling approaches for surveying specialised recreational fisheries - Shane P. Griffiths; Mitchell T. Zischke; Mark L. Tonks; Julian G. Pepperell; Sharon Tickell (Reviews in Fish Biology and Fisheries, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

The Effect of Nonideal Cascade Impactor Stage Collection Efficiency Curves on the Interpretation of the Size of Inhaler-Generated Aerosols - D. L. Roberts; J. P. Mitchell (AAPS PharmSciTech, 2013)

Stable carbon isotopic evidence for climate change across the late Pleistocene to early Holocene from Lesotho, southern Africa - P. ROBERTS; J. A. LEE‐THORP; P. J. MITCHELL; C. ARTHUR (Journal of Quaternary Science, 2013)
Although significant environmental and climatic changes are likely to have occurred across the Pleistocene/Holocene transition in southern Africa, records are sparse, with information regarding temperature change especially rare. We thus know little about the conditions facing Later Stone Age human populations at this time, particularly those in the highland interior where temperature shifts would have had strong impacts on floral and faunal distributions. In Lesotho, a well‐defined altitudinal distribution of C 3 and C 4 photosynthetic plant taxa, and their remains in soil organic matter, provides a means of estimating past temperature shifts. We applied this principle to stratified sediments from two archaeological sequences in the Lesotho lowlands ( c . 1600 m a.s.l.) to produce a palaeotemperature record focusing on the period 14 000–9500 cal a BP. The results show an overall trend from exclusively C 3 vegetation at the Last Glacial Maximum towards greater contributions of C 4 taxa, and thus warmer conditions, during the Holocene. However, large temperature fluctuations are evident within this trend, with rapid changes of up to 4 °C visible between 11 200 and 9500 cal a BP. The continued presence of hunter‐gatherers during this time suggests that the region must have remained attractive to human populations despite significant climatic instability and cool episodes. Copyright © 2013 John Wiley & Sons, Ltd.

Insect resistance of a full sib family of tetraploid switchgrass Panicum virgatum L. with varying lignin levels - Patrick F. Dowd; Gautam Sarath; Robert B. Mitchell; Aaron J. Saathoff; Kenneth P. Vogel (Genetic Resources and Crop Evolution, 2013)

Good Cascade Impactor Practice (GCIP) and Considerations for “In-Use” Specifications - S. C. Nichols; J. P. Mitchell; C. M. Shelton; D. L. Roberts (AAPS PharmSciTech, 2013)

A Decision Support Framework for Science-Based, Multi-Stakeholder Deliberation: A Coral Reef Example - Amanda P. Rehr; Mitchell J. Small; Patricia Bradley; William S. Fisher; Ann Vega; Kelly Black; Tom Stockton (Environmental Management, 2012)

Soil Carbon Sequestration by Switchgrass and No-Till Maize Grown for Bioenergy - Ronald F. Follett; Kenneth P. Vogel; Gary E. Varvel; Robert B. Mitchell; John Kimble (BioEnergy Research, 2012)

Genetic markers of ovarian follicle number and menopause in women of multiple ethnicities - Sonya M. Schuh-Huerta; Nicholas A. Johnson; Mitchell P. Rosen; Barbara Sternfeld; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2012)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Effect of Sampling Volume on Dry Powder Inhaler (DPI)-Emitted Aerosol Aerodynamic Particle Size Distributions (APSDs) Measured by the Next-Generation Pharmaceutical Impactor (NGI) and the Andersen Eight-Stage Cascade Impactor (ACI) - Hlack Mohammed; Daryl L. Roberts; Mark Copley; Mark Hammond; Steven C. Nichols; Jolyon P. Mitchell (AAPS PharmSciTech, 2012)

Elemental composition of sediments in Lake Jinzai, Japan: Assessment of sources and pollution - Faruque Ahmed; M. Hawa Bibi; Takashi Asaeda; Carl P. J. Mitchell; Hiroaki Ishiga; Takehiko Fukushima (Environmental Monitoring and Assessment, 2012)

Enzymatic digestion in stomachless fishes: how a simple gut accommodates both herbivory and carnivory - Ryan D. Day; Donovan P. German; Jennifer M. Manjakasy; Ingrid Farr; Mitchell Jay Hansen; Ian R. Tibbetts (Journal of Comparative Physiology B, 2011)

Using microsatellite diversity in wild Anegada iguanas (Cyclura pinguis) to establish relatedness in a captive breeding group of this critically endangered species - Adele A. Mitchell; Jennie Lau; Leona G. Chemnick; Elizabeth A. Thompson; Allison C. Alberts; Oliver A. Ryder; Glenn P. Gerber (Conservation Genetics, 2011)

Quantifying Actual and Theoretical Ethanol Yields for Switchgrass Strains Using NIRS Analyses - Kenneth P. Vogel; Bruce S. Dien; Hans G. Jung; Michael D. Casler; Steven D. Masterson; Robert B. Mitchell (BioEnergy Research, 2011)

Development of a multiplexed bead-based immunoassay for the simultaneous detection of antibodies to 17 pneumococcal proteins - S. Shoma; N. J. Verkaik; C. P. de Vogel; P. W. M. Hermans; S. van Selm; T. J. Mitchell; M. van Roosmalen; S. Hossain; M. Rahman; H. Ph. Endtz; W. J. B. van Wamel; A. van Belkum (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Product Lifecycle Approach to Cascade Impaction Measurements - Terrence P. Tougas; Dave Christopher; Jolyon Mitchell; Svetlana Lyapustina; Michiel Van Oort; Richard Bauer; Volker Glaab (AAPS PharmSciTech, 2011)

Differential involvement of hippocampal serotonin1A receptors and re-uptake sites in non-cognitive behaviors of Alzheimer’s disease - Mitchell K. P. Lai; Shirley W. Tsang; Margaret M. Esiri; Paul T. Francis; Peter T.-H. Wong; Christopher P. Chen (Psychopharmacology, 2011)

GPS tomography in the polar cap: comparison with ionosondes and in situ spacecraft data - Dimitry Pokhotelov; P. T. Jayachandran; Cathryn N. Mitchell; John W. MacDougall; Michael H. Denton (GPS Solutions, 2011)

Sustained cortical and subcortical neuromodulation induced by electrical tongue stimulation - Joseph C. Wildenberg; Mitchell E. Tyler; Yuri P. Danilov; Kurt A. Kaczmarek; Mary E. Meyerand (Brain Imaging and Behavior, 2010)

Herbicides for Establishing Switchgrass in the Central and Northern Great Plains - Robert B. Mitchell; Kenneth P. Vogel; John Berdahl; Robert A. Masters (BioEnergy Research, 2010)

Efficient Methods of Estimating Switchgrass Biomass Supplies - Marty R. Schmer; Robert B. Mitchell; Kenneth P. Vogel; Walter H. Schacht; David B. Marx (BioEnergy Research, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Barcoding bushmeat: molecular identification of Central African and South American harvested vertebrates - Mitchell J. Eaton; Greta L. Meyers; Sergios-Orestis Kolokotronis; Matthew S. Leslie; Andrew P. Martin; George Amato (Conservation Genetics, 2010)

Spatial and Temporal Effects on Switchgrass Stands and Yield in the Great Plains - M. R. Schmer; R. B. Mitchell; K. P. Vogel; W. H. Schacht; D.B. Marx (BioEnergy Research, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Interspecific interactions of the critically endangered Forest Owlet (Athene blewitti) - Reuven Yosef; Satish A. Pande; Amit P. Pawashe; Raju Kasambe; Lynette Mitchell (acta ethologica, 2010)

Shifting dispersal modes at an expanding species’ range margin - ALISA P. RAMAKRISHNAN; TRIESTE MUSIAL; MITCHELL B. CRUZAN (Molecular Ecology, 2010)

Deleterious activity of cultivated grasses (Poaceae) and residues on soilborne fungal, nematode and weed pests - James J. Stapleton; Charles G. Summers; Jeffrey P. Mitchell; Timothy S. Prather (Phytoparasitica, 2010)

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes - David P. Dimasi; Jern Y. Chen; Alex W. Hewitt; Sonja Klebe; Richard Davey; John Stirling; Elizabeth Thompson; Robin Forbes; Tiong Y. Tan; Ravi Savarirayan; David A. Mackey; Paul R. Healey; et al. (Human Genetics, 2010)

Improved Quality Control Metrics for Cascade Impaction Measurements of Orally Inhaled Drug Products (OIPs) - Terrence P. Tougas; David Christopher; Jolyon P. Mitchell; Helen Strickland; Bruce Wyka; Mike Van Oort; Svetlana Lyapustina (AAPS PharmSciTech, 2009)

A Contemporary Assessment of Change in Humid Tropical Forests - GREGORY P. ASNER; THOMAS K. RUDEL; T. MITCHELL AIDE; RUTH DEFRIES; RUTH EMERSON (Conservation Biology, 2009)
In recent decades the rate and geographic extent of land‐use and land‐cover change has increased throughout the world's humid tropical forests. The pan‐tropical geography of forest change is a challenge to assess, and improved estimates of the human footprint in the tropics are critical to understanding potential changes in biodiversity. We combined recently published and new satellite observations, along with images from Google Earth and a literature review, to estimate the contemporary global extent of deforestation, selective logging, and secondary regrowth in humid tropical forests. Roughly 1.4% of the biome was deforested between 2000 and 2005. As of 2005, about half of the humid tropical forest biome contained 50% or less tree cover. Although not directly comparable to deforestation, geographic estimates of selective logging indicate that at least 20% of the humid tropical forest biome was undergoing some level of timber harvesting between 2000 and 2005. Forest recovery estimates are even less certain, but a compilation of available reports suggests that at least 1.2% of the humid tropical forest biome was in some stage of long‐term secondary regrowth in 2000. Nearly 70% of the regrowth reports indicate forest regeneration in hilly, upland, and mountainous environments considered marginal for large‐scale agriculture and ranching. Our estimates of the human footprint are conservative because they do not resolve very small‐scale deforestation, low‐intensity logging, and unreported secondary regrowth, nor do they incorporate other impacts on tropical forest ecosystems, such as fire and hunting. Our results highlight the enormous geographic extent of forest change throughout the humid tropics and the considerable limitations of the science and technology available for such a synthesis.

Nitrogen supply from fertilizer and legume cover crop in the transition to no-tillage for irrigated row crops - Timothy A. Doane; William R. Horwath; Jeffrey P. Mitchell; Jim Jackson; Gene Miyao; Kent Brittan (Nutrient Cycling in Agroecosystems, 2009)

Subacute exposure to N-ethyl perfluorooctanesulfonamidoethanol results in the formation of perfluorooctanesulfonate and alters superoxide dismutase activity in female rats - Wei Xie; Qian Wu; Izabela Kania-Korwel; Job C. Tharappel; Sanjay Telu; Mitchell C. Coleman; Howard P. Glauert; Kurunthachalam Kannan; S. V. S. Mariappan; Douglas R. Spitz; Jamie Weydert; Hans-Joachim Lehmler (Archives of Toxicology, 2009)

Nodulation of Sesbania species by Rhizobium ( Agrobacterium ) strain IRBG74 and other rhizobia - Stephen P. Cummings; Prasad Gyaneshwar; Pablo Vinuesa; Frank T. Farruggia; Mitchell Andrews; David Humphry; Geoffrey N. Elliott; Andrew Nelson; Caroline Orr; Deborah Pettitt; Gopit R. Shah; Scott R. Santos; et al. (Environmental Microbiology, 2009)
Summary Concatenated sequence analysis with 16S rRNA, rpoB and fusA genes identified a bacterial strain (IRBG74) isolated from root nodules of the aquatic legume Sesbania cannabina as a close relative of the plant pathogen Rhizobium radiobacter (syn. Agrobacterium tumefaciens ). However, DNA:DNA hybridization with R. radiobacter , R. rubi , R. vitis and R. huautlense gave only 44%, 5%, 8% and 8% similarity respectively, suggesting that IRBG74 is potentially a new species. Additionally, it contained no vir genes and lacked tumour‐forming ability, but harboured a sym ‐plasmid containing nifH and nodA genes similar to those in other Sesbania symbionts. Indeed, IRBG74 effectively nodulated S. cannabina and seven other Sesbania spp. that nodulate with Ensifer ( Sinorhizobium )/ Rhizobium strains with similar nodA genes to IRBG74, but not species that nodulate with Azorhizobium or Mesorhizobium . Light and electron microscopy revealed that IRBG74 infected Sesbania spp. via lateral root junctions under flooded conditions, but via root hairs under non‐flooded conditions. Thus, IRBG74 is the first confirmed legume‐nodulating symbiont from the Rhizobium ( Agrobacterium ) clade. Cross‐inoculation studies with various Sesbania symbionts showed that S. cannabina could form fully effective symbioses with strains in the genera Rhizobium and Ensifer , only ineffective ones with Azorhizobium strains, and either partially effective ( Mesorhizobium huakii ) or ineffective ( Mesorhizobium plurifarium ) symbioses with Mesorhizobium . These data are discussed in terms of the molecular phylogeny of Sesbania and its symbionts.

The curse of taxonomic uncertainty in biogeographical studies of free‐living terrestrial protists: a case study of testate amoebae from Amsterdam Island - T. J. Heger; E. A. D. Mitchell; P. Ledeganck; S. Vincke; B. Van de Vijver; L. Beyens (Journal of Biogeography, 2009)
Aim A current debate in microbial biogeography contrasts two views concerning the distribution of free‐living microorganisms. The first view assumes a ubiquitous distribution, while the second assumes that at least some species have limited geographical distributions. We tested for limited geographical distributions by identifying testate amoebae morphospecies from an extremely remote oceanic island where the potential for endemism is high. Location Amsterdam Island, Indian Ocean. Methods Sixty moss and water samples collected from the top of the volcano to the lowland were investigated for their testate amoeba content. Due to taxonomic uncertainties among the Argynnia ( Nebela ) dentistoma species complex (including A. antarctica ), we also performed light and scanning electron microscopy investigations on the shell ultrastructure and biometric analyses on several specimens of this taxon. Results We identified a total of 43 testate amoeba taxa belonging to 15 genera. Only four testate amoeba taxa had previously been recorded on this island. Testate amoeba communities of Amsterdam Island are dominated by cosmopolitan ubiquitous euglyphid taxa such as Trinema lineare , Assulina muscorum and Corythion dubium . The length and width ranges for Argynnia dentistoma on Amsterdam Island overlap with other records of this species and of A. antarctica , suggesting that A. antarctica is not a distinct taxon. Main conclusions Although Amsterdam Island is among the most remote islands in the world, an extensive inventory of testate amoeba morphospecies provided no clear evidence for endemism. On the one hand, our detailed morphometric analysis of the A. dentistoma complex revealed that A. antarctica , a morphospecies previously suggested to display endemism, cannot be confidently distinguished from the cosmopolitan morphospecies A. dentistoma . On the other hand, five morphotaxa could not be identified with certainty and might represent new species, potentially with limited distribution. These examples illustrate how taxonomic uncertainties undermine biogeographical studies of testate amoebae. In order to allow better interpretation of morphology‐based testate amoeba distribution data, an assessment of genetic diversity among and within morphotaxa in relation to geographical distance for some common testate amoebae should be given high priority.

Global irrigated area map (GIAM), derived from remote sensing, for the end of the last millennium - Prasad S. Thenkabail; Chandrashekhar M. Biradar; Praveen Noojipady; Venkateswarlu Dheeravath; Yuanjie Li; Manohar Velpuri; Muralikrishna Gumma; Obi Reddy P. Gangalakunta; Hugh Turral; Xueliang Cai; Jagath Vithanage; Mitchell A. Schull; et al. (International Journal of Remote Sensing, 2009)

Woody plant encroachment impacts on soil carbon and microbial processes: results from a hierarchical Bayesian analysis of soil incubation data - Jessica M. Cable; Kiona Ogle; Anna P. Tyler; Mitchell A. Pavao-Zuckerman; Travis E. Huxman (Plant and Soil, 2009)

Comparison of distinct protein isoforms of the receptor for advanced glycation end-products expressed in murine tissues and cell lines - Julia V. Gefter; Angel L. Shaufl; Mitchell P. Fink; Russell L. Delude (Cell and Tissue Research, 2009)

The Abbreviated Impactor Measurement (AIM) Concept: Part II—Influence of Evaporation of a Volatile Component—Evaluation with a “Droplet-Producing” Pressurized Metered Dose Inhaler (pMDI)-Based Formulation Containing Ethanol as Cosolvent - J. P. Mitchell; M. W. Nagel; V. Avvakoumova; H. MacKay; R. Ali (AAPS PharmSciTech, 2009)

The Abbreviated Impactor Measurement (AIM) Concept: Part 1—Influence of Particle Bounce and Re-Entrainment—Evaluation with a “Dry” Pressurized Metered Dose Inhaler (pMDI)-Based Formulation - J. P. Mitchell; M. W. Nagel; V. Avvakoumova; H. MacKay; R. Ali (AAPS PharmSciTech, 2009)

Phylogenetic relationships of Geranium species indigenous to New Zealand - A. D. Mitchell; P. B. Heenan; A. M. Paterson (New Zealand Journal of Botany, 2009)
New Zealand species of Geranium are shown to be closely related, forming a monophyletic group. Relationships inferred from Bayesian and NeighborNet analyses of internal and external transcribed spacer sequences generally agreed and were congruent with those inferred from study of morphological characters. Two groups of species (G. brevicaule and G. retrorsum groups) are well supported based on morphology and DNA sequence data. A third group, referred to as the G. microphyllum group, is recognised based on morphology but is only partially supported by the DNA sequence data. The DNA sequence and morphological variability in each of the G. brevicaule, G. microphyllum , and G. retrorsum groups support the recognition of additional taxonomic entities from New Zealand, but further study is required to address these issues. Furthermore, additional sampling of Australian and South American species of Geranium must be carried out before a taxonomic re‐evaluation can be made of sections Andina and Chilensia .

Groundwater Demand Management in the Great Lakes Basin—Directions for New Policies - Satya P. Mohapatra; Anne Mitchell (Water Resources Management, 2009)

Switchgrass Biomass Simulation at Diverse Sites in the Northern Great Plains of the U.S. - J. R. Kiniry; M. R. Schmer; K. P. Vogel; R. B. Mitchell (BioEnergy Research, 2008)

Soil Carbon Storage by Switchgrass Grown for Bioenergy - M. A. Liebig; M. R. Schmer; K. P. Vogel; R. B. Mitchell (BioEnergy Research, 2008)

Evidence for multiple sources of invasion and intraspecific hybridization in Brachypodium sylvaticum (Hudson) Beauv. in North America - DAVID M. ROSENTHAL; ALISA P. RAMAKRISHNAN; MITCHELL B. CRUZAN (Molecular Ecology, 2008)
We compared the levels and distribution of genetic diversity in Eurasian and North American populations of Brachypodium sylvaticum (Huds.) Beauv. (false brome), a newly invasive perennial bunchgrass in western North America. Our goals were to identify source regions for invasive populations, determine the number of independent invasion events, and assess the possibility that postinvasion bottlenecks and hybridization have affected patterns of genetic diversity in the invaded range. We tested the hypothesis that this Eurasian grass was accidentally introduced into two areas in Oregon and one site in California by examining nuclear microsatellites and chloroplast haplotype variation in 23 introduced and 25 native populations. In the invaded range, there was significantly lower allelic richness ( R S ), observed heterozygosity ( H O ) and within‐population gene diversity ( H S ), although a formal test failed to detect a significant genetic bottleneck. Most of the genetic variation existed among populations in the native range but within populations in the invaded range. All of the allelic variation in the invaded range could be explained based on alleles found in western European populations. The distribution of identified genetic clusters in the North American populations and the unique alleles associated with them is consistent with two historical introductions in Oregon and a separate introduction to California. Further analyses of population structure indicate that intraspecific hybridization among genotypes from geographically distinct regions of western Europe occurred following colonization in Oregon. The California populations, however, are more likely to be derived from one or perhaps several genetically similar regions in the native range. The emergence and spread of novel recombinant genotypes may be facilitating the rapid spread of this invasive species in Oregon.

Prevalence of virus-like particles within a staghorn scleractinian coral (Acropora muricata) from the Great Barrier Reef - N. L. Patten; P. L. Harrison; J. G. Mitchell (Coral Reefs, 2008)

Sulfate exports from multiple catchments in a glaciated forested watershed in western New York, USA - Shreeram P. Inamdar; Myron J. Mitchell (Environmental Monitoring and Assessment, 2008)

A powder neutron diffraction study of the crystal structure of the fluoroperovskite NaMgF3 (neighborite) from 300 to 3.6 K - Roger H. Mitchell; Malcolm Alexander; Lachlan M. D. Cranswick; Ian P. Swainson (Physics and Chemistry of Minerals, 2007)

Purification and characterization of rhodobactin: a mixed ligand siderophore from Rhodococcus rhodochrous strain OFS - Suraj Dhungana; Ryszard Michalczyk; Hakim Boukhalfa; Joseph G. Lack; Andrew T. Koppisch; Jason M. Fairlee; Mitchell T. Johnson; Christy E. Ruggiero; Seth G. John; Matthew M. Cox; Cindy C. Browder; Jennifer H. Forsythe; et al. (BioMetals, 2007)

The Keylong Serai rock avalanche, NW Indian Himalaya: geomorphology and palaeoseismic implications - W. A. Mitchell; M. J. McSaveney; A. Zondervan; K. Kim; S. A. Dunning; P. J. Taylor (Landslides, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Urban Influences on Stream Chemistry and Biology in the Big Brushy Creek Watershed, South Carolina - Gregory P. Lewis; Jennifer D. Mitchell; C. Brannon Andersen; Dennis C. Haney; Min-Ken Liao; Kenneth A. Sargent (Water, Air, & Soil Pollution, 2007)

Comparison between ATSR‐2 stereo, MOS O 2 ‐A band and ground‐based cloud top heights - C. Naud; K. L. Mitchell; J.‐P. Muller; E. E. Clothiaux; P. Albert; R. Preusker; J. Fischer; R. J. Hogan (International Journal of Remote Sensing, 2007)

Stereo cloud‐top heights and cloud fraction retrieval from ATSR‐2 - J.‐P. Muller; M.‐A. Denis; R. D. Dundas; K. L. Mitchell; C. Naud; H. Mannstein (International Journal of Remote Sensing, 2007)

A case of true hermaphroditism reveals an unusual mechanism of twinning - Vivienne L. Souter; Melissa A. Parisi; Dale R. Nyholt; Raj P. Kapur; Anjali K. Henders; Kent E. Opheim; Daniel F. Gunther; Michael E. Mitchell; Ian A. Glass; Grant W. Montgomery (Human Genetics, 2007)

Natural variation and conservation of Lepidium sisymbrioides Hook, f. and L. solandri Kirk (Brassicaceae) in South Island, New Zealand, based on morphological and DNA sequence data - P. B. Heenan; A. D. Mitchell; P. A. McLenachan; P. J. Lockhart; P. J. de Lange (New Zealand Journal of Botany, 2007)
The South Island, New Zealand, endemics Lepidium sisymbrioides and L. solandri are accepted at species rank. L. solandri Kirk is reinstated and includes L. matau Petrie in synonymy, and L. kawarau is reduced to synonymy of L. sisymbrioides . Twenty‐nine floral and vegetative morphological characters were measured and used for analyses of character variation and principal components analysis. Leaf characters proved to be the most useful in distinguishing between L. sisymbrioides and L. solandri , with 12 of the 15 leaf characters having significantly different means. Only 7 of the 14 floral characters included in the study have significantly different means. In comparison to L. solandri, L. sisymbrioides has longer and narrower terminal and primary pinnae and cauline leaves, more secondary pinnae and cauline leaf lobes, less hairy sepals and ovaries, narrower ovaries, and shorter filaments. L. sisymbrioides occurs on rock outcrops in the upper Manuherikia, Waitaki, and Kawarau river valleys. L. solandri grows mainly on alluvium and outwash gravels in semi‐arid parts of inland Canterbury and Central Otago. DNA sequence data from ITS, ETS, and trnL‐trnF markers were used to examine phylogenetic patterns in L. sisymbrioides and L. solandri , and the related species L. kirkii, L. naufragorum , and L. tenuicaule . There is substantial variation in these markers in L. sisymbrioides and L. solandri , and this is considered to be due to introgression from other species of Lepidium , such as L. kirkii and L. tenuicaule . Much of the variation in the ETS sequences occurs in samples of L. sisymbrioides and L. solandri from the Manuherikia River valley, and this can be attributed to geneflow with the sympatric L. kirkii . Lepidium sisymbrioides and L. solandri are considered to be “Acutely Threatened, Nationally Endangered” using the New Zealand threatened plant classification criteria. In this assessment both species are considered to be data poor. Further field survey for new populations is required.

Phylogenetic assignment and mechanism of action of a crop growth promoting Rhizobium radiobacter strain used as a biofertiliser on graminaceous crops in Russia - David R. Humphry; Mitchell Andrews; Scott R. Santos; Euan K. James; Lioubov V. Vinogradova; Liamara Perin; Veronica M. Reis; Stephen P. Cummings (Antonie van Leeuwenhoek, 2007)

Quantifying anthropogenic influence on recent near-surface temperature change - M. R. Allen; N. P. Gillett; J. A. Kettleborough; G. Hegerl; R. Schnur; P. A. Stott; G. Boer; C. Covey; T. L. Delworth; G. S. Jones; J. F. B. Mitchell; T. P. Barnett (Surveys in Geophysics, 2006)

Plastid genome characterisation in Brassica and Brassicaceae using a new set of nine SSRs - M. L. Flannery; F. J. G. Mitchell; S. Coyne; T. A. Kavanagh; J. I. Burke; N. Salamin; P. Dowding; T. R. Hodkinson (Theoretical and Applied Genetics, 2006)

The crystal structure of Deinococcus radiodurans Dps protein (DR2263) reveals the presence of a novel metal centre in the N terminus - Célia V. Romão; Edward P. Mitchell; Sean McSweeney (JBIC Journal of Biological Inorganic Chemistry, 2006)

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades - Michael S. Ross; Sherry Mitchell-Bruker; Jay P. Sah; Stuart Stothoff; Pablo L. Ruiz; David L. Reed; Kris Jayachandran; Charles L. Coultas (Hydrobiologia, 2006)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Tantalum-bearing titanite: synthesis and crystal structure data - Ruslan P. Liferovich; Roger H. Mitchell (Physics and Chemistry of Minerals, 2006)

An assessment of the genetic diversity and structure within and among populations of wild pigs (Sus scrofa) from Australia and Papua New Guinea - P. B. S. Spencer; J. Hampton; S. J. Lapidge; J. Mitchell; J. Lee; J. R. Pluske (Journal of Genetics, 2006)

Variants in Deleted in AZoospermia-Like (DAZL) are correlated with reproductive parameters in men and women - Joyce Y. Tung; Mitchell P. Rosen; Lawrence M. Nelson; Paul J. Turek; John S. Witte; Daniel W. Cramer; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2006)

An oral carcinogenicity and toxicity study of senna (Tinnevelly senna fruits) in the rat - J. M. Mitchell; U. Mengs; S. McPherson; J. Zijlstra; P. Dettmar; R. Gregson; J. C. Tigner (Archives of Toxicology, 2006)

Hydrogeomorphic Controls on Reduction–Oxidation Conditions across Boreal Upland–Peatland Interfaces - Carl P. J. Mitchell; Brian A. Branfireun (Ecosystems, 2005)

Analysis of expressed sequence tags and the identification of associated short tandem repeats in switchgrass - Christian M. Tobias; Paul Twigg; Daniel M. Hayden; Kenneth P. Vogel; Rob M. Mitchell; Gerard R. Lazo; Elaine K. Chow; Gautam Sarath (Theoretical and Applied Genetics, 2005)

Rhombohedral ilmenite group nickel titanates with Zn, Mg, and Mn: synthesis and crystal structures - Ruslan P. Liferovich; Roger H. Mitchell (Physics and Chemistry of Minerals, 2005)

Crystal chemistry of titanite-structured compounds: the CaTi1-xZrxOSiO4 (x≤0.5) series - Ruslan P. Liferovich; Roger H. Mitchell (Physics and Chemistry of Minerals, 2005)

PUP PRODUCTION AND POPULATION TRENDS OF THE AUSTRALIAN FUR SEAL (ARCTOCEPHALUS PUSILLUS DORIFERUS) - Roger Kirkwood; Rosemary Gales; Aleks Terauds; John P. Y. Arnould; David Pemberton; Peter D. Shaughnessy; Anthony T. Mitchell; John Gibbens (Marine Mammal Science, 2005)

Solid solution of rare earth elements in synthetic titanite: a reconnaissance study - R. P. Liferovich; R. H. Mitchell (Mineralogy and Petrology, 2005)

Design, Synthesis and Evaluation of Trisubstituted Thiazoles Targeting Plasmodium Falciparum Cysteine Proteases - P. Mallikarjun Goud; Anjaneyulu Sheri; Prashant V. Desai; E. Blake Watkins; Babu Tekwani; Yogesh Sabnis; Jiri Gut; Philip J. Rosenthal; Mitchell A. Avery (Medicinal Chemistry Research, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Recovery of saccadic dysmetria following localized lesions in monkey superior colliculus - Doug P. Hanes; Mitchell K. Smith; Lance M. Optican; Robert H. Wurtz (Experimental Brain Research, 2005)

Depositional and post‐depositional history of warm stage deposits at Knocknacran, Co. Monaghan, Ireland: implications for preservation of Irish last interglacial deposits - A. P. M. Vaughan; L. A. Dowling; F. J. G. Mitchell; S.‐E. Lauritzen; A. M. McCabe; P. Coxon (Journal of Quaternary Science, 2004)
Organic‐rich deposits, uncovered during overburden removal from mantled gypsum karst at Knocknacran opencast gypsum mine, Co. Monaghan, are the best candidate to date for a last interglacial record in Ireland. The two till and organic‐rich deposits (preserved at different quarry elevations) were emplaced on to a Tertiary dolerite surface during high‐energy flood events and subsequently folded and faulted by movement towards sinkholes in underlying gypsum. Uranium–thorium disequilibrium dating suggests that the organic‐rich deposits in the upper section were hydrologically isolated at ca. 41 ka and those in the lower section at ca. 86 ka. Interpretation of the pollen content, although tentative because of the depositional and post‐depositional history of the material, suggests that the organic material originated in a warm stage possibly warmer than the post‐Eemian interstadials. The unusual setting of preservation may indicate that in situ , last interglacial deposits have generally been removed by erosion in Ireland. Copyright © 2004 John Wiley & Sons, Ltd.

Rapid predictions of cold tolerance in Douglas-fir seedlings using chlorophyll fluorescence after freezing - Michael P. Perks; Bruce A. Osborne; Derek T. Mitchell (New Forests, 2004)

Arthropodium bifurcatum (Asparagaceae), a new species from northern New Zealand - P. B. Heenan; A. D. Mitchell; P. J. de Lange (New Zealand Journal of Botany, 2004)
Anthropodium bifurcatum is a new species described from northern New Zealand, being currently known from a number of mainland sites as well as offshore islands, including the Poor Knights Islands and Three Kings Islands. It is segregated from A. cirratum and distinguished from that species by its thicker and upright leaves with a fleshy white midrib, abaxial surface of the leaves with irregular protrusions, bifurcate flower bracts, and larger fruit. Amplified Fragment Length Polymorphism DNA data are congruent with morphology in supporting the revised classification. A. bifurcatum is considered to have a conservation status of “Gradual Decline” using the New Zealand Threat Classification System.

Microsatellite identification and characterization in peanut (A. hypogaea L.) - M. E. Ferguson; M. D. Burow; S. R. Schulze; P. J. Bramel; A. H. Paterson; S. Kresovich; S. Mitchell (Theoretical and Applied Genetics, 2004)

Uptake of nitrogen by rice studied with a 15N point-placement technique - J.E. Sheehy; M. Mnzava; K.G. Cassman; P.L. Mitchell; P. Pablico; R.P. Robles; A. Ferrer (Plant and Soil, 2004)

Leukotrienes mediate 5-hydroxytryptamine-induced plasm extravasation in the rat knee joint via CysLT-type receptors - Y. Wang; J. Mitchell; M. Sharma; A. Gabriel; K. Moriyama; P. Pierce Palmer (Inflammation Research, 2004)

Aerodynamic particle size analysis of aerosols from pressurized metered-dose inhalers: Comparison of andersen 8-stage cascade impactor, next generation pharmaceutical impactor, and model 3321 aerodynamic particle sizer aerosol spectrometer - Jolyon P. Mitchell; Mark W. Nagel; Kimberly J. Wiersema; Cathy C. Doyle (AAPS PharmSciTech, 2003)

Designing Effective Marine Protected Areas in Seaflower Biosphere Reserve, Colombia, Based on Biological and Sociological Information - A. FRIEDLANDER; J. SLADEK NOWLIS; J. A. SANCHEZ; R. APPELDOORN; P. USSEGLIO; C. McCORMICK; S. BEJARANO; A. MITCHELL‐CHUI (Conservation Biology, 2003)
Ecologists have paid increasing attention to the design of marine protected areas (MPAs), and their design advice consistently recommends representing all habitat types within MPAs or MPA networks as a means to provide protection to all parts of the natural ocean system. Recent developments of new habitat‐mapping techniques make this advice more achievable, but the success of such an approach depends largely on our ability to define habitat types in a way that is ecologically relevant. We devised and tested the ecological relevance of a set of habitat‐type definitions through our participation in a stakeholder‐driven process to design a network of MPAs, focusing on no‐take marine reserves in the Seaflower Biosphere Reserve, San Andrés Archipelago, Colombia. A priori definitions of habitat types were ecologically relevant, in that our habitat‐type definitions corresponded to identifiable and unique characteristics in the ecological communities found there. The identification of ecological pathways and connectivity among habitats also helped in designing ecologically relevant reserve boundaries. Our findings contributed to the overall design process, along with our summary of other general principles of marine reserve design. Extensive stakeholder input provided information concerning the resources and their patterns of use. These inputs also contributed to the reserve design process. We anticipate success for the Seaflower Biosphere Reserve at achieving conservation and social goals because its zoning process includes detailed yet flexible scientific advice and the participation of stakeholders at every step .

Regeneration of Rhizophora mangle in a Caribbean mangrove forest: interacting effects of canopy disturbance and a stem-boring beetle - Wayne P. Sousa; Swee P. Quek; Betsy J. Mitchell (Oecologia, 2003)

Phylogeny, biogeography and adaptive radiation of Pachycladon (Brassicaceae) in the mountains of South Island, New Zealand - P. B. Heenan; A. D. Mitchell (Journal of Biogeography, 2003)
Aim To report analyses and propose hypotheses of adaptive radiation that explain distributional patterns of the alpine genus Pachycladon Hook.f. – a morphologically diverse genus from New Zealand closely related to Arabidopsis thaliana . Location South Island, New Zealand. Methods Morphological and nrDNA ITS sequence phylogenies were generated for Pachycladon . An analysis is presented of species distributional patterns and attributes. Results Phylogenetic analyses of morphological characters and nrDNA ITS sequence data were found to be congruent in supporting three New Zealand clades for Pachycladon . Monophyletic groups identified within the genus are geographically distinct and are associated with different geological parent materials. Distribution maps, latitude and altitude range, and data on geological parent material are presented for the nine named and one unnamed species of Pachycladon from New Zealand. Main conclusions (a) Panbiogeographic hypotheses accounting for the origin and present‐day distribution of Pachycladon in New Zealand are not supported. (b) Species diversity and distributions of Pachycladon are explained by a Late Tertiary–Quaternary adaptive radiation associated with increasing specialization to geological substrates. Pachycladon cheesemanii Heenan & A.D.Mitch. is morphologically similar to the closest overseas relatives. It is a geological generalist and has wide latitudinal and altitudinal ranges, and we suggest it resembles the ancestral form of the genus in New Zealand. Pachycladon novae‐zelandiae (Hook.f.) Hook.f. and P. wallii (Carse) Heenan & A.D.Mitch. are a southern South Island group that predominantly occurs on Haast Schist, are polycarpic, have lobed leaves, and lateral inflorescences. Pachycladon enysii (Cheeseman) Heenan & A.D.Mitch., P. fastigiata (Hook.f.) Heenan & A.D.Mitch., and P. stellata (Allan) Heenan & A.D.Mitch. are restricted to greywacke in the eastern South Island, and are facultatively monocarpic, have serrate leaves, and stout terminal inflorescenes. (c) Present distributions of Pachycladon species may relate to Pleistocene climate change. Pachycladon enysii reaches the highest altitude of New Zealand species of Pachycladon and is most common in the Southern Alps in Canterbury. We propose that this species survived on nunataks at the height of the last glaciation. In contrast, P. fastigiata grows at a lower altitude and is absent from the high mountains of the Southern Alps. We suggest it was extirpated from this area during the last glaciation.

Impacts of changing climate and atmospheric deposition on N and S drainage losses from a forested watershed of the Adirondack Mountains, New York State - Ji‐Hyung Park; Myron J. Mitchell; Patrick J. McHale; Sheila F. Christopher; Tilden P. Meyers (Global Change Biology, 2003)
Biogeochemical responses to changing climate and atmospheric deposition were investigated using nitrogen (N) and sulfur (S) mass balances, including dry deposition and organic solutes in the Arbutus Lake watershed in the Adirondack Mountains, New York State. Long‐term monitoring of wet‐only precipitation (NADP/NTN, 1983–2001) and dry deposition (AIRMoN, 1990–2001) at sites adjacent to the watershed showed that concentrations of SO 4 2− in precipitation, SO 4 2− in particles,and SO 2 vapor all declined substantially ( P 4 + in precipitation, HNO 3 vapor, and particulate NO 3 − ), except for NO 3 − in precipitation, which showed a small decrease in the late 1990s. From 1983 to 2001, concentrations of SO 4 2− in the lake outlet significantly decreased (−2.1 μeq L −1 yr −1 , P 3 − and dissolved organic N (DON) concentrations showed no consistent temporal trends. With the inclusion of dry deposition and DON fluxes into the mass balance, the retained portion of atmospheric N inputs within the main subcatchment increased from 37% to 60%. Sulfur outputs greatly exceeded inputs even with the inclusion of dry S deposition, while organic S flux represented another source of S output, implying substantial internal S sources. A significant relationship between the annual mean concentrations of SO 4 2− in lake discharge and wet deposition over the last two decades ( r =0.64, P 4 2− concentrations, despite substantial internal S sources. By contrast, interannual variations in both NO 3 − concentrations and fluxes in lake discharge were significantly related to year‐to‐year changes in air temperature and runoff. Snowmelt responses to winter temperature fluctuations were crucial in explaining large portions of interannual variations in watershed NO 3 − export during the months preceding spring snowmelt (especially, January–March). Distinctive response patterns of monthly mean concentrations of NO 3 − and DON in the major lake inlet to seasonal changes in air temperature also suggested climatic regulation of seasonal patterns in watershed release of both N forms. The sensitive response of N drainage losses to climatic variability might explain the synchronous patterns of decadal variations in watershed NO 3 − export across the northeastern USA.

Light Transmittance Estimates in a Longleaf Pine Woodland - Michael A. Battaglia; Robert J. Mitchell; Paul P. Mou; Stephen D. Pecot (Forest Science, 2003)
While the importance of canopy structure in open woodlands and savannas on regulating the flow of energy and matter is well known, few studies have investigated how variation in overstory abundance influences canopy light transmission and the extent that estimates vary in their ability to characterize the light environment in these ecosystems. Canopy light transmittance (% photosynthetic photon flux density, or %PPFD) was measured with gallium arsenide phosphide (GaAsP) photodiodes and was monitored throughout the growing season in an open-canopy longleaf pine (Pinus palustris Mill.) woodland across an overstory abundance gradient. Several estimates of canopy light transmittance were also measured, including 10 minute averages of %PPFD under clear and overcast sky conditions during summer, fall, and winter, as well as light estimates derived from hemispherical photographs (gap fraction, GF: gap light index, GLI; and weighted canopy openness, WCO). Linear and curvilinear regression were used to analyze the relationship between (1) light measurements and canopy structure and (2) light estimates and growing-season % PPFD measured by light diodes. Of all light measurements in this study, ten-minute average % PPFD measurements during clear days were the most variable: only a small proportion in the 10-minute average of light reaching the understory was correlated to either overstory structure or growing-season canopy transmittance. While measures on overcast days improved the correlations, they tended to overestimate transmittance. Gap fraction (GF) and gap light index (GLI) were strongly correlated with % PPFD and overstory structure, and the relationship between GLI and % PPFD was improved by using a direct light setting of 60%. In addition to strong correlation, hemispherical photographic estimates of light fell along a 1:1 line with % growing-season PPFD; thus, estimates were relatively unbiased. Measures of light in this ecosystem need to incorporate the large spatial and temporal variation in light transmittance that is characteristic of this ecosystem if investigators are to understand the relationship between open-canopy woodlands and their light environments.

Propagule size and predispersal damage by insects affect establishment and early growth of mangrove seedlings - Wayne P. Sousa; Peter G. Kennedy; Betsy J. Mitchell (Oecologia, 2003)

Reduced hybrid cluster proteins (HCP) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at high resolution using synchrotron radiation - David Aragão; Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Ming Y. Liu; Carlos Frazão; Lígia M. Saraiva; António V. Xavier; Jean LeGall; Walter M. A. M. van Dongen; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

Water requirements of subsurface drip-irrigated faba bean in California - David R. Bryla; Gary S. Bañuelos; Jeff P. Mitchell (Irrigation Science, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

5-Hydroxytryptamine-induced plasma extravasation in the rat knee joint is mediated by multiple prostaglandins - G. Xie; Y. Wang; M. Sharma; A. Gabriel; J. Mitchell; Y. Xing; T. Meuser; P. Pierce Palmer (Inflammation Research, 2003)

Molecular systematics of the New Zealand Pachycladon (Brassicaceae) complex: Generic circumscription and relationships to Arabidopsis sens. lat. and Arabis sens. lat. - P. B. Heenan; A. D. Mitchell; M. Koch (New Zealand Journal of Botany, 2002)
Nuclear ribosomal DNA ITS sequence data were used to assess the relationships of Cheesemania, Ischnocarpus, and Pachycladon to each other and to other genera in the Brassicaceae. Phylogenetic analyses are congruent with other studies that infer the Pachycladon complex (including Pachycladon, Cheesemania, and Ischnocarpus) is monophyletic. The complex occurs within an Arabidopsoid clade that includes Arabidopsis and the recently recognised segregate genera Beringia, Crucihimalaya, Olimarabidopsis, and Pseudoarabidopsis, and the Arabis segregates Boechera and Turritis. The Pachycladon complex is sister to Beringia and Crucihimalaya, and forms a distinct New Zealand lineage. Molecular clock estimates suggest the Pachycladon complex diverged from its nearest relatives between 1.0 and 3.5 million years ago. The close relationship of Cheesemania, Ischnocarpus, and Pachycladon is reflected in low ( Pachycladon to include species placed in Cheesemania and Ischnocarpus. New combinations are made in Pachycladon for species previously placed in Cheesemania and Ischnocarpus. A new name, P. cheesemanii, is presented for Ischnocarpus novae‐zelandiae as that species epithet is preoccupied in Pachycladon.

Effects of nitric oxide synthase inhibitors on the febrile response to muramyl dipeptide and lipopolysaccharide in rats - Kamerman P.; Mitchell D.; Laburn H. (Journal of Comparative Physiology B, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Comment: Cosmogenic radionuclide dating of glacial landforms in the Lahul Himalaya, northern India: defining the timing of Late Quaternary glaciation. L. A. Owen, L. Gualtieri, R. C. Finkel, M. W. Caffee, D. I. Benn and M. C. Sharma (2001). (Journal of Quaternary Science 16 : 555–563) - P. J. Taylor; W. A. Mitchell (Journal of Quaternary Science, 2002)

Prestress Due to Dimensional Changes Caused by Demineralization: A Potential Mechanism for Microcracking in Bone - Yener N. Yeni; Mitchell B. Schaffler; Gary Gibson; David P. Fyhrie (Annals of Biomedical Engineering, 2002)

Introgression and stabilization oferwinia tuber soft rot resistance into potato after somatic hybridization ofsolanum tuberosum ands. brevidens - J. Mitchell McGrath; Christie E. Williams; Geraldine T. Haberlach; Susan M. Wielgus; Thomas F. Uchytil; John P. Helgeson (American Journal of Potato Research, 2002)

How are climate and marine biological outbreaks functionally linked? - Marshall L. Hayes; Joseph Bonaventura; Todd P. Mitchell; Joseph M. Prospero; Eugene A. Shinn; Frances Van Dolah; Richard T. Barber (Hydrobiologia, 2001)

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)

Classifying tree planters and non planters in a subsistence farming system using a discriminant analytical approach - A. K. Mahapatra; C. P. Mitchell (Agroforestry Systems, 2001)

Factors regulating the downstream migration of mature eels ( Anguilla spp.) at Aniwhenua Dam, Bay of Plenty, New Zealand - Jacques A. Boubée; Charles P. Mitchell; Benjamin L. Chisnall; Dave W. West; Eddie J. Bowman; Alex Haro (New Zealand Journal of Marine and Freshwater Research, 2001)
The downstream migrations of mature longfinned eels ( Anguilla dieffenbachii Gray, 1842) and shortfinned eels ( Anguilla australis Richardson, 1848) were investigated at Aniwhenua Dam on the Rangitaiki River between 1992 and 1998. Migrants were mostly females over 1000 mm total length (TL) with otoliths indicating rapid growth rates. Migrations, which occurred on a few nights each autumn, generally began once water temperatures began to decline and ended when temperatures dropped below c. 11 °C. Rainfall and flow increases were found to be key factors triggering migration events. Rainfall exceeding a cumulative total of 40 mm over 3 days accounted for 60% of migrant eels arriving at Aniwhenua. It is proposed that such rainfall triggers could be used as predictors to instigate mitigation activities that would allow mature eels to proceed uninjured past barriers such as hydro‐electric dams.

Phylogenetic characterization of epibiotic bacteria in the accessory nidamental gland and egg capsules of the squid Loligo pealei (Cephalopoda: Loliginidae) - Elena Barbieri; Bruce J. Paster; Deborah Hughes; Ludek Zurek; Duane P. Moser; Andreas Teske; Mitchell L. Sogin (Environmental Microbiology, 2001)
Sexually mature female squid Loligo pealei harbour dense bacterial communities in their accessory nidamental glands (ANGs) and in their egg capsules (ECs). This study describes a molecular approach using the 16S rRNA gene (rDNA) to identify bacterial populations within the ANG and the ECs of the North Atlantic squid species L. pealei . Fluorescent in situ hybridization (FISH) and 16S rDNA analysis showed that predominantly alpha‐ and, to a lesser extent, gamma‐proteobacteria were the predominant components of the ANG and EC bacterial communities. Sequencing results showed the presence of alpha‐proteobacterial populations affiliated with the Roseobacter group and additional deep‐branching alphaproteobacterial lineages. In contrast, isolates from the ANG and ECs contained only a few alpha‐proteobacteria of the Roseobacter group compared with several gamma‐proteobacterial isolates, mostly Shewanella and Pseudoalteromonas species. Most of the ANG‐associated bacterial populations were also found within the ECs of L. pealei . The molecular approach allowed the visualization of alpha‐proteobacteria as major constituents of a bacterial symbiosis within the reproductive system of the Loliginidae.

Proteomic analysis reveals a novel set of cell wall proteins in a transformed tobacco cell culture that synthesises secondary walls as determined by biochemical and morphological parameters - Kristopher A. Blee; Edward R. Wheatley; Victoria A. Bonham; Geoffrey P. Mitchell; Duncan Robertson; Antoni R. Slabas; Michael M. Burrell; Przemyslaw Wojtaszek; G. Paul Bolwell (Planta, 2001)

Risedronate Pharmacokinetics and Intra- and Inter-Subject Variability Upon Single-Dose Intravenous and Oral Administration - David Y. Mitchell; William H. Barr; Rachelle A. Eusebio; Karen A. Pallone Stevens; Frank P. Duke; Darrell A. Russell; John D. Nesbitt; James H. Powell; Gary A. Thompson (Pharmaceutical Research, 2001)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Optimal detection and attribution of climate change: sensitivity of results to climate model differences - G. C. Hegerl; P. A. Stott; M. R. Allen; J. F. B. Mitchell; S. F. B. Tett; U. Cubasch (Climate Dynamics, 2000)

Crystal chemistry of perovskite-type compounds in the tausonite-loparite series, (Sr 1−2 x Na x La x )TiO 3 - R. H. Mitchell; A. R. Chakhmouradian; P. M. Woodward (Physics and Chemistry of Minerals, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

IDENTIFYING DIURNAL FORAGING HABITAT OF ENDANGERED HAWAIIAN MONK SEALS USING A SEAL‐MOUNTED VIDEO CAMERA - Frank A. Parrish; Mitchell P. Craig; Timothy J. Ragen; Gregory J. Marshall; Birget M. Buhleier (Marine Mammal Science, 2000)
A bstract The Hawaiian monk seal ( Monachus schauinslandi ) is thought to be a foraging generalist, preying on numerous species in diverse habitats of the subtropical Northwestern Hawaiian Islands. At the atoll of French Frigate Shoals, recent evidence of emaciation and low survival in monk seals prompted a search for their specific prey communities and foraging habitat. A video camera (National Geographic Television's CRITTERCAM) fitted to 24 adult male seals documented benthic and demersal foraging on the deep slopes (50‐80 m) of the atoll and neighboring banks. The number of bottom searches for prey was compared by year, time of day, type of bottom, individual seal, and length of bottom time. Analysis of variance identified a significant interaction of seal and bottom type, explaining 65% of the total variance. Seals fed on communities of cryptic fauna (fish and large invertebrates) in transitional “ecotone” regions of low relief where consolidated substrate, rubble, and talus bordered areas of sand. Independent areal surveys of bottom types throughout the atoll and neighboring banks suggest that the type of bottom selected as foraging habitat represents a relatively small percentage of the total benthic area available.

Modelling the recent historical impacts of atmospheric CO 2 and climate change on Mediterranean vegetation - C. P. Osborne; P. L. Mitchell; J. E. Sheehy; F. I. Woodward (Global Change Biology, 2000)
Summary During the past century, annual mean temperature has increased by 0.75°C and precipitation has shown marked variation throughout the Mediterranean basin. These historical climate changes may have had significant, but presently undefined, impacts on the productivity and structure of sclerophyllous shrubland, an important vegetation type in the region. We used a vegetation model for this functional type to examine climate change impacts, and their interaction with the concurrent historical rise in atmospheric CO 2 . Using only climate and soil texture as data inputs, model predictions showed good agreement with observations of seasonal and regional variation in leaf and canopy physiology, net primary productivity (NPP), leaf area index (LAI) and soil water. Model simulations for shrubland sites indicated that potential NPP has risen by 25% and LAI by 7% during the past century, although the absolute increase in LAI was small. Sensitivity analysis suggested that the increase in atmospheric CO 2 since 1900 was the primary cause of these changes, and that simulated climate change alone had negative impacts on both NPP and LAI. Effects of rising CO 2 were mediated by significant increases in the efficiency of water‐use in NPP throughout the region, as a consequence of the direct effect of CO 2 on leaf gas exchange. This increase in efficiency compensated for limitation of NPP by drought, except in areas where drought was most severe. However, while water was used more efficiently, total canopy water loss rose slightly or remained unaffected in model simulations, because increases in LAI with CO 2 counteracted the effects of reduced stomatal conductance on transpiration. Model simulations for the Mediterranean region indicate that the recent rise in atmospheric CO 2 may already have had significant impacts on productivity, structure and water relations of sclerophyllous shrub vegetation, which tended to offset the detrimental effects of climate change in the region.

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the north american great lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

The limited extent of plume-lithosphere interactions during continental flood-basalt genesis: geochemical evidence from Cretaceous magmatism in southern Brazil - S. A. Gibson; R. N. Thompson; O. H. Leonardos; A. P. Dickin; J. G. Mitchell (Contributions to Mineralogy and Petrology, 1999)

BODY SIZE, SURVIVAL, AND DECLINE OF JUVENILE HAWAIIAN MONK SEALS, MONACHUS SCHAUINSLANDI - Mitchell P. Craig; Timothy J. Ragen (Marine Mammal Science, 1999)
A bstract In the mid 1980s half of the entire Hawaiian monk seal species was located at French Frigate Shoals, and this colony may have reached environmental carrying capacity. Since 1989 this colony has declined by 55%, primarily from poor juvenile survival. Only 8%–25% of weaned pups have survived to age 2 during this period, compared to at least 80% between 1984 and 1987. We characterize (1) this drop in survival, (2) a strong, but variable, correlation between survival and size at weaning, (3) interisland differences in size from weaning to age 2 in 1991 through 1993, and (4) decadal‐scale changes in mean measures of size at weaning. We compare observations at French Frigate Shoals with the colony at Laysan Island where abundance is well below historical levels and was therefore expected to be below carrying capacity. At Laysan Island juvenile survival has also been poor (30%‐70%), and the size of weaned pups has decreased during the past decade. Our hypothesis is that poor survival may be due to reduced prey availability at both sites, but particularly at French Frigate Shoals. Evidence to support this hypothesis includes a large increase in total abundance at French Frigate Shoals; reduced size of weaned pups; decreased survival, emaciation, and slower growth rates of juvenile seals; and declining primary productivity. Regardless of cause, the immediate consequences at French Frigate Shoals and Laysan Island, and for the species overall, will likely be poor recruitment and productivity. Because the decline is still in progress, the ultimate consequences for the species' viability are of great concern in light of its already low abundance.

Uncertainty Analysis of Regional Mercury Exposure - C. Seigneur; K. Lohman; P. Pai; K. Heim; D. Mitchell; L. Levin (Water, Air, & Soil Pollution, 1999)

New Insights into Disintegrin Metalloproteases - T. J. Carty; L. L. LoPresti-Morrow; P. G. Mitchell; P. A. McNiff; K. F. McClure (Inflammation Research, 1999)

Potential for artefacts in the measurement of fructose and sucrose in extracts of potato tubers using the microplate reader assay - S. Mitchell; P. Dobson; H. V. Davies; R. Viola (Potato Research, 1998)

Variant in sulfonylurea receptor-1 gene is associated with high insulin concentrations in non-diabetic Mexican Americans: SUR-1 gene variant and hyperinsulinemia - Denise L. Goksel; Kathryn Fischbach; Ravindranath Duggirala; Braxton D. Mitchell; Lydia Aguilar-Bryan; John Blangero; M. P. Stern; Peter O’Connell (Human Genetics, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

DNA damage induced by ultraviolet radiation in coral-reef microbial communities - M. M. Lyons; P. Aas; J. D. Pakulski; L. Van Waasbergen; R. V. Miller; D. L. Mitchell; W. H. Jeffrey (Marine Biology, 1998)

TRP64ARG β3-adrenergic receptor and obesity in Mexican Americans - K. Silver; Braxton D. Mitchell; Jeremy Walston; J. D. Sorkin; Michael P. Stern; Jesse Roth; A. R. Shuldiner (Human Genetics, 1997)

Competition between birds and mammals: A comparison of giving-up densities between crested larks and gerbils - Joel S. Brown; Burt P. Kotler; William A. Mitchell (Evolutionary Ecology, 1997)

Activity, blood temperature and brain temperature of free-ranging springbok - Duncan Mitchell; Shane K. Maloney; Helen P. Laburn; Michael H. Knight; Gernot Kuhnen; Claus Jessen (Journal of Comparative Physiology B, 1997)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

A study of feral carp, Cyprinus carpio L., exposed to Microcystis aeruginosa at Lake Mokoan, Australia, and possible implications for fish health - C R Carbis; G T Rawlin; P Grant; G F Mitchell; J W Anderson; I McCauley (Journal of Fish Diseases, 1997)
Feral carp, Cyprinus carpio L., were collected at bimonthly intervals for 12 months from Lake Wellington, where there was no evidence of significant growth of Microcystis aeruginosa . Various blood parameters of these carp were measured to ascertain the normal range values for feral carp in this region. A similar study was conducted at Lake Mokoan, where M. aeruginosa formed a visible scum that contained detectable levels of microcystins for 4 consecutive months. Carp were taken from Lake Mokoan each month, and the histology and blood biochemistry of the fish were examined for indications of microcystin toxicity. During February, March and April, 66% of the carp from Lake Mokoan had livers with widespread hepatocyte atrophy, and 37% of the fish had gills with pinpoint necrosis, epithelial ballooning, folded lamellar tips and exfoliation of the lamellar epithelium. Compared to carp from Lake Wellington, the serum aspartate aminotransferase activity and the serum bilirubin concentrations of carp from Lake Mokoan were elevated during January, February, March and April. The data were consistent with impaired hepatocyte function in some carp from Lake Mokoan. Serum sodium and chloride concentrations in carp from Lake Mokoan were lower than those for carp at Lake Wellington from December to April, indicating that most carp from Lake Mokoan had difficulty maintaining cation‐anion homeostasis during this period. Nevertheless, carp at Lake Mokoan always appeared healthy, and no mortalities were reported.

Hormone-sensitive lipase (Lipe): Sequence analysis of the 129Sv mouse Lipe gene - R. Sztrolovics; S. P. Wang; P. Lapierre; H. S. Chen; M -F. Robert; G. A. Mitchell (Mammalian Genome, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Competitive regimes and female bonding in two species of squirrel monkeys (Saimiri oerstedi and S. sciureus) - Carol L. Mitchell; Sue Boinski; Carel P. van Schaik (Behavioral Ecology and Sociobiology, 1991)

Zonal and meridional circulations in the equatorialzone as deduced from the divergence field of the surface wind - Wang Shaowu; Todd P. Mitchell; John M. Wallace (Advances in Atmospheric Sciences, 1987)

Lymphocytotoxic and microbial antibodies in Crohn's disease and matched controls - D. Gump; E. Caul; O. Eade; H. Greenberg; A. Kapikian; B. MacPherson; P. Mitchell; K. Parent; S. Richmond; W. Beeken (Antonie van Leeuwenhoek, 1981)

Peripheral neuropathy following intraneural injection of mercury compounds - J. Mitchell; P. J. Gallagher (Archives of Toxicology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Relative concentrations of14C-DDT and of two polychlorinated biphenyls in the lipids of cod tissues after a single oral dose - A. I. Mitchell; P. A. Plack; I. M. Thomson (Archives of Environmental Contamination and Toxicology, 1977)